Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2022)
A dataset containing 375594737 species occurrences available in GBIF matching the query: { "and" : [ "Geometry POLYGON((-26.89453 34.91747,22.32422 34.91747,22.32422 52.50619,-26.89453 52.50619,-26.89453 34.91747))", "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present" ] } The dataset includes 375594737 records from 9785 constituent datasets: 783 records from Gestion Patrimoniale de la Corniche Basque - Suivi Hivernale des Oiseaux Communs. 1 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. 65 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 15 records from New Zealand Arthropod Collection (NZAC). 112 records from Sorensen distance for herbivores. 8974 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Mise en place d'un suivi scientifique des odonates pour la production d’indicateurs de biodiversité. 50 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 429 records from Suivi et inventaire de la réserve naturelle de Saucats - La Brède - Suivi Temporel des Oiseaux Communs par Échantillonnage Ponctuel Simple (protocole STOC-EPS). 1 records from Revision of the subgenus Nessus of the genus Hypocaccus from Central Europe, with description of a new species (Coleoptera: Histeridae). 263 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Florent HERVOUET. 36 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Etude écologique de la Cité Scolaire Paul Valéry Paris 12ème. 84 records from Birdrace-Die_Nachtraben-Stuttgart. 87 records from Artenvielfalt des "Grünen Klassenzimmers". 516 records from Museu de Ciències Naturals de Barcelona: BGJBB. 55 records from Waldsee. 5 records from Hydromedusae observed during night dives in the Gulf Stream. 115 records from Plan de gestion 2017 - 2021 du site des Landes humides de Mazerolles (64) mené par le CEN Nouvelle-Aquitaine - Observations d'odonates (imagos) réalisées par le CEN Aquitaine selon le protocole STELI. 26524 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 89 records from Occurrence of mammalia relicts at site Pod hradem. 141 records from Inventaire biodiversité du site Pierre Fabre d'Aignan. 1045806 records from Belgian IFBL Flora Checklists (1939-1971). 684 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 913 records from Programme les sentinelles du climat - effets du changement climatique sur la biodiversité en région Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 13 records from Projet de parc éolien sur la commune d'Envronville - Données faune terrestre. 476 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 156 records from Collections of Bioclass, school #179, Moscow. 17 records from Réseau Loup - Lynx ONCFS - Lynx 1988 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 72 records from Mammalia (Luomus). 988 records from flower availability 2008 Alb-korrigiert. 42 records from Inventaire des Octocoralliaires des fonds sédimentaires de la région niçoise. 26 records from Calcareous dinocysts in ODP Hole 80-550B, part 1. 1297 records from Plan de gestion 2015-2020 de la tourbière de Passeben - Inventaire et suivi Faune. 403 records from Plan de gestion 2014 - 2018 du site de la butte de Launay (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1170 records from Gestion Patrimoniale de la Corniche Basque - Suivi Temporel des Oiseaux Communs Echantillion Ponctuel Simple. 25207 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données multi sources collectées par Hanot Christophe, pour l'atlas des Cerambycidae de métropole (lot 2017). 147 records from Range table from benthic foraminifers in ODP Hole 161-974B. 36 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 4 records from Plan de gestion 2016 - 2020 du site des Coteaux de Saint-Victor et Montagrier (24) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 96 records from Inventaire participatif Chauves souris du littoral - Données du GCA saisies sur Faune Aquitaine. 140 records from Revision of the morphology, phylogenetic relationships, behaviour and diversity of the Iberian and Italian ant-like Tachydromia Meigen, 1803 (Diptera: Hybotidae). 138 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - données de la collection personnelle de CHASSAIN Jacques. 30 records from On the origin and diversification of the stygobiotic freshwater snail genus Hauffenia (Caenogastropoda: Hydrobiidae) with special focus on the northern species and the description of two new species. 1360 records from Relative abundances of dinoflagellate cysts in several IODP and DSDP holes. 3621 records from Mesures compensatoires sur des projets de Collectivités territoriales - Données CEN L-R Compensation collectivités. 874 records from Plasm bearing foraminifera counts of multinet M21/1_MSN603. 18 records from Naturtag. 45 records from données espèces - Expertise IPE 63. 178 records from EDP Foz Tua: Bat Habitats - Complementary Studies [2010]. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 163783 records from Inventaire des oiseaux nicheurs de France métropolitaine 2009-2012 - Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 4 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de BLANC Josselyne. 709 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Atelier de malacologie continentale, 13-14 septembre (Corrèze et Dordogne). Société Limousine d’Étude des Mollusques (SLEM). 43 records from Brown University. 8 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Adeline AIRD. 5 records from Grasses of the Forest Herbarium Ibadan (FHI) Nigeria. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de DUFOUR Daniel. 1017 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Inventaire Mollusques RNR Chalmessin 2019. 251 records from Monitoring of colonial waterfowl species (2013-2014). 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 39 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 152 (N.S) n°45 (2), 2017 - Données faune. 760 records from Total foraminifera counts of multinet M21/2_MSN650. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Jean-Luc CASTETS. 1211 records from Wintering wildfowl in Portugal – 1992-1993. 1 records from Eight species in the Nebela collaris complex: Nebela gimlii (Arcellinida, Hyalospheniidae), a new species described from a Swiss raised bog. 2 records from Plan de gestion 2012 - 2016 du site des Landes humides de Mazerolles (64) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 128 records from Tetranychus urticae collection records in a predator-prey system: Phytoseiulus persimilis (Acari: Phytoseiidae) and Tetranychus urticae (Acari: Tetranychidae). 5 records from DMNS Egg Collection (Arctos). 10 records from A new genus and species of Haplobainosomatidae (Diplopoda: Chordeumatida) from the MSS of the Sierra de Guadarrama National Park, central Spain. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 836 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de HAURAY Yann (SAPROX). 1546 records from Données d'odonates récoltées en 2013 et 2014 par le CEN Aquitaine - Suivi Temporel des Libellules (STELI) / PRAO 2013 - 2017. 470 records from (Table 8) Distribution of planktonic foraminifera in the late Cretaceous and Eocene to early Miocene sections of ODP Hole 149-899B. 154 records from EDP Foz Tua: Black Wheatear (Oenanthe leucura) (Aves) - Ecological Monitoring Program [2012-2017]. 8 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 1 records from Coelogynopora schockaerti n. sp. (Proseriata: Coelogynoporidae), a remnant of a platyhelminth coldwater fauna in the northwestern Mediterranean?. 76 records from Orthoptera - SMF. 5462 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 414 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (3), 2009 - Données faune. 760 records from Total foraminifera counts of multinet M21/2_MSN628. 31 records from Inventaire des amphibiens en milieux humides sur le site de Fay-sur-Lignon. 2 records from Monograph of the Staphylinidae of Crete (Greece). Part I. Diversity and endemism (Insecta: Coleoptera). 100 records from Plan de gestion 2017 - 2021 du site «Coteaux de Brungidour et des Foncillières» (24) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 23 records from Notes on Mediterranean Theridiidae (Araneae) – II. 2 records from University of Vermont, Pringle Herbarium, North American lichens. 2085 records from Regroupement d'études et d'inventaires - Inventaire et suivi Odonates. 3010 records from Programmes de connaissance sur les zones humides d'Occitanie - Données ANA - CEN Ariège sur les zones humides (occurences de taxons). 957 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 1 records from Happywhale - Long-finned Pilot Whale in North Atlantic Ocean. 3 records from Bryophyte Herbarium (H): Herbarium Fennoscandiae orientalis. 34 records from Collection Coleoptera SMF. 346 records from SCANS II cetacean sightings on primary platform of vessel surveys 2005. 4 records from Plan de gestion 2019 - 2023 du site des Grottes de Sare (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 181 records from Spießwoogtal / Königsbruch (Fischbach). 727 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive draine 1999 - 2003 Coordonnées GPS Lambert 93. 1 records from Plan de gestion 2017 - 2021 de la Réserve Naturelle Régionale d'Errota Handia (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 778 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2010 - 2014 Coordonnées GPS Lambert 93. 68 records from Centrale Hydroélectrique de Port à l'Anglais. 2560 records from KTU Pteridophyta. 95 records from Ortelsbruch - Hangmoor bei Morbach. 166 records from Plecoptera. 18 records from Plan de gestion 2014 - 2020 du site des Landes de Sault-de-Navailles (64) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1567 records from Données d'expertise convention GTM Bâtiment et le Service du patrimoine naturel du MNHN. 184 records from Plan de gestion 2017 - 2021 du site des Coteaux du Légal (24) mené par le CEN Aquitaine - Observations ornithologiques (Indice Ponctuel d'Abondance) réalisées par Vya Natura (étude de l'avifaune nicheuse). 13 records from Atlas de la Biodiversité Communales sur la Communauté de Commune de Montesquieu - Observations faunistiques fortuites réalisées par Locusta. 2 records from Water striders (Heteroptera: Gerromorpha: Gerridae) of Romania with an update on the distribution of Gerris gibbifer and G. maculatus in southeastern Europe. 8 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Thorsen ANDRONIK. 5 records from Animation du Plan d'Actions pour la préservation et la valorisation des zones humides des lacs Médocains - Inventaire opportuniste. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 7066 records from Field Museum of Natural History (Botany) Fungi Collection. 7 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 470 records from 59 - Beau Gui Avifaune. 26279 records from Inventaire de la flore de Gironde 2014-2019 - Inventaire de la flore de Gironde 2018. 120 records from BIRDRACE The early birds. 2125 records from Regroupement d'études et d'inventaires - Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 70 records from ONCFS Réseau Ours brun - Ours 2010 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 1 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 61 records from Protozoa Abundance_Microbial Parameters. 93757 records from National Plant Monitoring Scheme - England, Scotland, Wales. 3176 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Fabien LE NOUVEL. 4 records from Projet du parc éolien de la Voie des Prêtres 2 - Mammifères inventoriés de manière fortuite en 2017. 6475 records from SEWBReC Amphibians (South East Wales). 2497 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données malacologiques des membres du Collectif GERMAIN. 199 records from Inventaires de la faune exotique envahissante - Sciences participatives sur les espèces animales introduites (EEE-FIF). 1138 records from Lajitietokeskus/FinBIF - Notebook, general observations. 2050 records from Occurrences de mammifères du Groupe Mammalogique Normand (GMN) - Occurrence de Carnivores du Groupe Mammalogique Normand (GMN). 69 records from Schulgarten mit Klasse 8a (Essen). 9656 records from SILENE-FAUNE-PACA - Ecosphère_2017_12_18. 596 records from Colección Orthoptera y Dermaptera Antonio del Cerro (Museo de Zoología Ibérica Antonio Notario) UPM. 473 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Tellez David provenant de la base de donnée du SINP Île-de-France CETTIA. 794 records from Isle of Wight non-native invasive species. 1 records from Weber State University Herbarium. 78 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Anna Even. 12 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Zoosystema [1997- ]. 4944 records from Atlas / Observatoire des Mammifères de Bretagne - Données Ongulés et Lagomorphes en Bretagne de 2000 à 2016. 43 records from KYMA boat-based surveys in Thyrrhenian Sea and Ionian Sea. 2145 records from Mayfly (Ephemeroptera) records from Britain and Ireland, via iRecord. 5 records from Regroupement d'études et inventaires - Suivi Pies-grièches. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 377 records from Inventaires et suivis faune - Inventaire et suivi des libellules – Protocole STELI. 148 records from Plan de gestion 2019 - 2023 de la Réserve Naturelle Régionale de l’Étang de Chourroumillas (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 123 records from Birdrace-SportfreundeTriller-Münster. 4722 records from Atlas of Bats from Continental Portugal 2013. 45643 records from Données Faune Base SIRFF - FNE Centre-Val de Loire - Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 5361 records from Réseau de suivi des macro-invertébrés aquatiques - Inventaire et suivi Macroinvertébrés. 6 records from Données naturalistes de MICHELOT MARC. 5 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 8 records from Plan de gestion 2019 - 2023 du site des Grottes de Sare (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Nouvelle-Aquitaine. 68 records from Streuobstwiese. 4947 records from SIM-Fungal records compiled by Joan Montón. 271 records from Western Australian Museum provider for OZCAM. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 164 records from Colección de Hongos del Herbario de la Universidad de La Laguna: TFC Mic. 1267681 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 272751 records from NRW Regional Data: South East Wales Non-sensitive species. 3 records from First records of Edwardsiana sociabilis (Ossiannilsson, 1936) and Laburrus pellax (Horváth, 1903) (Hemiptera, Auchenorrhyncha: Cicadellidae) in Switzerland. 278 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Joana PERRODIN. 1 records from New species and records of Paraphloeostiba Steel, 1960 from China and Laos and descriptions of four new species of related genera (Coleoptera: Staphylinidae Omaliinae: Omaliini). 62 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Wroza Stanislas provenant de la base de donnée du SINP Île-de-France CETTIA. 28 records from Hainbachtal bei Oelsnitz / V.. 1012 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 2012 - 2016 Coordonnées GPS Lambert 93. 162 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction 63-150 µm. 1 records from Russian Barnacle Geese (aggregated per 1-degree cell). 4632 records from Inventaire de la flore de la Vienne 2009-2018 - Inventaire de la flore du Grand Poitiers 2009. 1 records from University of Hawaii Insect Museum. 1429 records from Inventaire de la faune vertébrés du Parc national du Mercantour - Inventaire de la faune de vertébrés du Parc national du Mercantour. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Olivier DELZONS. 5 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Monique CASTEX. 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 106 records from BIRDRACE Bon(n)apartemöwen. 66 records from Réseau Loup - Lynx ONCFS - Lynx 2002 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 26 records from FERME ÉOLIENNE DE BLANZAY - Avifaune Blanzay hiver 2017. 11 records from Plan de gestion 2013 - 2017 du site des Coteaux de Pujols (33) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 874 records from Total foraminifera counts of multinet M21/1_MSN603. 721 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette des champs 2011 - 2015 Coordonnées GPS Lambert 93. 19 records from Landesgartenschau. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 151 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Oiseaux patrimoniaux - Inventaire non standardisé - LPO74. 870 records from Mycology herbarium, UiT Tromsø Museum. 1932 records from University of Minnesota Insect Collection. 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 279489 records from ARABEL - Arachnologia Belgica. 63067 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 203 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Conventionnement Groupement Forestier des Visaubes. 424 records from Expertise dans le cadre d'une sollicitation liée à une étude d'impact - Données études d'impact CEN M-P. 455 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 4 records from MLZ Bird Collection (Arctos). 274 records from Bernhardsthal. 4871 records from Alnitak-Alnilam Cetaceans and sea turtles surveys off Southern Spain. 126 records from Naturschutzgebiet Müchelholz (Mücheln). 166 records from Wiese am Waldrand (Gurtweil). 168 records from Centrale photovoltaïque de Sainte-Julie - données environnementales de Sainte-Julie. 107 records from Veille écologique - Suivi des papillons de jour. 16 records from Sea Turtles of Dominica (aggregated per 1-degree cell). 1 records from A taxonomic review of the genus Amicta Heylaerts, 1881 in North Africa, Near and Middle East (Lepidoptera, Psychidae, Oiketicinae, Acanthopsychini). 10 records from Occurrence of mammalia relicts at site Ochtendung. 136 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure ACOREP provenant de la base de donnée du SINP Île-de-France CETTIA. 338 records from EDP Foz-Tua: Fishes – Ecological Monitoring Program [2011-2017]. 21200 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 2 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Arnoul MATEO. 18 records from Occurrence of mammalia relicts at site Ochoz Cave. 15 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire des mammifères du Parc de la Haute-Île (93). 42 records from Meiofauna abundance in sediment core 13077-014. 134 records from Canadian Museum of Nature Herbarium. 2706 records from Plan de gestion de la Réserve Naturelle Régionale de la Massonne - Inventaire de données. 691 records from Banco de Germoplasma del Real Jardín Botánico Juan Carlos I. 1 records from A new species of Dolichopoda (Orthoptera: Rhaphidophoridae; Dolichopodainae) from Western Greece. 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 371 records from Bannwald Burghauser Forst. 948 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Bulletin du Muséum d'Histoire Naturelle [1895- ]. 62 records from TRANSMED cétacés - Données Cétacés Transmed. 25470 records from SEWBReC Bees, Wasps and Ants (South East Wales). 290 records from Données du Comité Départemental de Protection de la Nature et de l'Environnement de Loir-et-Cher (CDPNE) - Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 12 records from Flora und Fauna am Mühlberg. 127 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 145 (N.S) n° 38 (2), 2010 - Données faune. 123 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive littorne 2007 - 2011 Coordonnées GPS Lambert 93. 733 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette des champs 2006 - 2010 Coordonnées GPS Lambert 93. 1564 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur Pratz Jean-Louis. 986 records from (Table T4) Planktonic foraminiferal stratigraphy of ODP Hole 173-1069A sediments. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 108 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Communauté d’Agglomération Grand Paris Sud provenant de la base de donnée du SINP Île-de-France CETTIA. 279 records from Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 2314 records from Midden-Limburg Fish Ponds Survey. 252 records from Demande de renouvellement et d'extension d'autorisation de carrière au titre de la rubrique 2510 des ICPE - Carrière de Villemanoche (89) - Donnees biodiversite carriere Villemanoche 181210. 23 records from NU: KwaZulu-Natal Invasive Alien Species (1821-2011). 35132 records from Herbarium Senckenbergianum (FR) - Fungi. 3593 records from National System of Protected Areas in Poland - Animals. 271 records from Norfish: Irish Herring Fishery 1520-1790. 325 records from Plan de gestion 2016 - 2020 du site du vallon du Clamondé (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 360 records from Rhinophoridae Recording Scheme - verified via iRecord. 20 records from Distribution of meiobenthos in sediment core M23_123 (2) of the northeastern Atlantic (Table 1). 903 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Geometridae de France métropolitaine. 4 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 16678 records from Suivi Temporel des Libellules (STELI). 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 2161 records from Conventions de partenariat sur les terrains militaires d'Occitanie - Données convention de gestion CEN MP - autorités du camp militaire (Camp de Ger). 28 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Observation d'amphibiens réalisées par le CEN Aquitaine dans le cadre du suivi des passages petite faune. 24 records from ONCFS Réseau Ours brun - Ours 2016 présence Régulière Mailles 10km LAEA Réseau Ours brun ONCFS. 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 1 records from Taxonomic revision of the Palaearctic Tetramorium chefketi species complex (Hymenoptera: Formicidae).. 24 records from Inventaire en continu de la ZNIEFF 'Coteaux de Saint-Cernin-de-l'Herm' - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 43 records from SILENE-FAUNE-PACA - GPMM_Environnement_2017_12_18. 660 records from MICA - Muskrat occurrences collected by RATO in East Flanders, Belgium. 6 records from Empria and Monsoma in Japan. 24 records from Ibaraki Nature Museum, Vascular Plants collection. 14 records from Plan de gestion multi-site 2020 - 2024 des lagunes d'Hourtin (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 309 records from Diversity of Spiders from Azorean Trails. 99 records from Inventaires et suivis programme Lagunes mené par le Département des Landes - Ensemble des données Orthoptères. 6102 records from United Kingdom National Whale Stranding Database 1913-2008. 36803 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Christophe CHAMBOLLE. 10385 records from Inventaire de la flore de Charente-Maritime 2012-2020 - Inventaire de la flore de Charente-Maritime 2018. 5868 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 2012 records from Pollen profile RAC20, Lake Racou, France. 11 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Laurent ROUSSERIE. 103 records from BIRDRACE Resopal-Darmstadt-Dieburg. 3661 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 11 records from Revision of Brada Stimpson, 1853, and Bradabyssa Hartman, 1967 (Annelida, Flabelligeridae). 2808 records from Base BOMBINA du Parc Naturel régional Lorraine - Natura 2000 Vallée de la Seille. 212 records from Inventaires et suivis effectués sur les retenues collinaires de l'Institution Adour - Inventaire sur la retenue collinaire du Brousseau (commune de AIRE-SUR-L'ADOUR). 1 records from Onuphi s and Mooreonuphis (Annelida: Onuphidae) from West Africa with the description of three new species and the reinstatement of O. landanaensis Augener, 1918. 992 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pigeon ramier 2006 - 2010 Coordonnées GPS Lambert 93. 1704 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Anita GEORGES. 792 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 715 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 10 records from Hydraena (s.str.) dinarica, new species (Coleoptera: Hydraenidae) along with further records of Hydraena spp. from Durmitor National Park, Montenegro and comments on the DNA barcoding problem with the genus. 13 records from DSMZ Collection of Filamentous Fungi and Yeasts. 19 records from Genetic variation of the 30 beech stands across three exploratories. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Caitlin DAGG. 9007 records from Bryophyte diversity in forests. 3 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 76 records from BIRDRACE Nachtigallen. 325 records from Triebesbach (Zeulenroda-Triebes). 65 records from Réseau Loup - Lynx ONCFS - Lynx 2016 présence Occasionnelle Mailles_10km_LAEA Réseau Loup-Lynx ONCFS. 61 records from Inventaire des Lépidoptères Rhopalocères et Zygènes de France métropolitaine - Données de Midi-Pyrénées transmises par Pascal Peyrache.. 12 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 14 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de THÉVENOT Jessica. 27 records from Occurrence of mammalia relicts at site Biedermann. 1119 records from (Table 5) Distribution of planktonic foraminifera in the latest Pliocene to Holocene section of ODP Hole 149-898A. 2 records from Re-classification of Lycoriella Frey sensu lato (Diptera, Sciaridae), with description of Trichocoelina gen. n. and twenty new species. 35145 records from Inventaire de la flore de Lot-et-Garonne 2013-2018 - Inventaire de la flore de Lot-et-Garonne 2017. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 7178 records from Florient - a database dealing with historic wild plant occurrences. 117 records from Inventaire chiroptérologique dans les Chataigneraies du PNRPL - Inventaire bioaccoustique et capture au filet de chiroptères en verger à châtaignes 2019. 99 records from Wiese und Weide am Waldrand von Gusterath. 29 records from Lucanidae. 90 records from Plan de gestion du Marais du Logit - Inventaire opportuniste Faune. 460 records from Unna-Mühlhausen, Wiesen. 705 records from IBF Monitoring of Plant Galls. 54 records from Renouvellement-Extension de la carrière de MONTPOUILLAN - Inventaire flore. 158 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 87 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Occasionnelle du Loup en 2009. 1 records from Three endemic Aphaenogaster from the Siculo-Maltese archipelago and the Italian Peninsula: part of a hitherto unrecognized species group from the Maghreb? (Hymenoptera: Formicidae: Myrmicinae). 101 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de LE GLOANEC Vincent. 59 records from Inventaire de la flore de Charente 2013-2015 - Inventaire de la flore de Charente 2014. 330 records from Benthic macrofauna abundance of sediment core 13200-008. 26 records from Réseau Loup - Lynx ONCFS - Lynx 1999 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 21 records from Plan régional d'actions en faveur des odonates (PRAO) : 4ème phase (2019 - 2020) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine (Étude Leucorrhines). 1 records from New insights into polyphyly of the harpacticoid genus Delavalia (Crustacea, Copepoda) through morphological and molecular study of an unprecedented diversity of sympatric species in a small South Korean bay. 2366 records from Données biodiversité Ferme éolienne de St Mard. 24 records from Occurrence of mammalia relicts at site Wildenscheuer Cave. 7672 records from River Biologists' Database (EPA). 9 records from Occurrence of mammalia relicts at site Brühl 1. 190095 records from Tiroler Landesmuseum Ferdinandeum. 67 records from Tongrube bei Hettstedt. 1227 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 13864 records from Données de l'association Nature 18 - Données faune Nature 18 - 2017. 912 records from Total foraminifera counts of multinet M21/1_MSN605. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 6056 records from Odonata records from RSPB Reserves 1970-2009. 10426 records from The BCT/MTUK Bats & Roadside Mammals Survey. 844 records from Données supplémentaires Atlas des Mammifères marins. 31709 records from Phenology and biological traits of migrating salmon (Salmo salar) sampled by trapping in the survey in the Oir river (France). 53 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 4489 records from ATBI Parc national du Mercantour / Parco naturale Alpi Marittime - Observations floristiques PNM issues de la base de données flore du Conservatoire botanique national alpin. 147 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 120 records from Données espèces - Expertise IPE 79. 124378 records from NBIS Records to December 2016. 1 records from A new species of Aphelocheirus (Hemiptera: Heteroptera: Aphelocheiridae) from Morocco. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 624 records from Projet de parc éolien des Portes du Nivernais - Données d'inventaires écologiques faube-flore. 4605 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 81 records from SILENE-FAUNE-PACA - Métropole_Nice_Côte_d'Azur_2017_12_18. 7963 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de MOREAU Patrice. 84 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 3139 records from Trawl-survey data in the central-eastern Adriatic Sea (Mediterranean) collected in 1957 and 1958. 257 records from Advanced Modelling & Research on Eutrophication & the Structure of coastal planktonic food-webs: mechanisms & modelling (AMORE). 40 records from ONCFS Réseau Ours brun - Ours 2005 présence Régulière Mailles 10km LAEA Réseau Ours brun ONCFS. 1930 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 15 records from Meiofauna abundance in sediment core 54301-010. 310014 records from Programme d’acquisition et de valorisation de données naturalistes BioObs - Observations naturalistes des Amis de BioObs.. 24139 records from Millipede (Diplopoda) records for Britain and Ireland to 2005. 12 records from Marine metagenome ICM_AWP. 1 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 611 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Quentin ROME. 269 records from SEWBReC Springtails and allies (South East Wales). 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 4516 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Vindras Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 5421 records from UK Biodiversity Action Plan Invertebrate Data for Wales. 97 records from BIRDRACE NABUhu Trier!. 910 records from Inventaire de la flore de la Vienne 2009-2018 - Inventaire de la flore de la Vienne 2015. 1293 records from InsectScale2008FlowerCover. 136 records from Plants galls. 131 records from Artenvielfalt auf dem Schulgelände. 22514 records from Neptune Deep-Sea Microfossil Occurrence Database. 2 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 193 records from Plan de gestion 2013 - 2018 du site des Coteaux de Las Hies (64) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 22179 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Alain Noël. 2 records from The millipede genus Leucogeorgia Verhoeff, 1930 in the Caucasus, with descriptions of eleven new species, erection of a new monotypic genus and notes on the tribe Leucogeorgiini (Diplopoda: Julida: Julidae). 2 records from Revision of the genus Lindholmiola HESSE, 1931 (Gastropoda: Pulmonata: Helicodontidae). 24 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 147 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Laurence Beauchamp. 31 records from Ladybirds of Ireland. 50 records from Collections ichtyologiques et herpétologiques (BOUM). 3 records from Rutgers University, Chrysler Herbarium - Lichen Collection. 14756 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Bruno OGER. 138 records from Collection Gilles Becquet (BOUM). 40 records from Occurrence of mammalia relicts at site Felsställe. 23 records from Migration and foraging ecology of Greater Shearwater (aggregated per 1-degree cell). 82 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 271 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 125 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 2 records from Systematic notes on some leptomedusa species with a description of Neotima galeai n. spec. (Hydrozoa, Cnidaria). 895 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Olivier BARDET. 94 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2008. 2829 records from Pollen profile ADR353. 58372 records from Fichier communal des ongulés. 90 records from Ecological study of the fish fauna near the mouth of the Zwin in 1985 and 1986. 1348 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Bulletin de la Société d'Histoire naturelle de Colmar. 6 records from Sächsische Schweiz (Pfaffenstein). 138 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pigeon colombin 2005 - 2009 Coordonnées GPS Lambert 93. 1171 records from Glasaalmigratie - Glass eel migration in the river Yser. 17 records from Plan de gestion 2019 - 2023 du site des Coteaux de Las Hies (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 43 records from Projet éolien de Saint-Barbant - Autre faune. 503 records from Programme les sentinelles du climat - effets du changement climatique sur la biodiversité en région Nouvelle-Aquitaine - Observations d'odonates réalisées par le CPIE Seignanx et Adour selon le protocole STELI adapté pour le programme. 69 records from Naturpark Kottenforst-Ville 18.6.09. 4 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 87 records from Living Cirripedia. 19606 records from Programmes de connaissance sur les milieux secs d'Occitanie - Données CEN M-P Milieux secs. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 35493 records from SILENE-FAUNE-PACA - DDT05_2017_12_18. 10 records from New species of Pseudoscorpiones (Arachnida) from tree hollows in a Mediterranean oak forest in Spain. 84 records from Roter Berg Werdau (Leubnitz). 218 records from Land and freshwater molluscs of Northern Spain. 65 records from Mauernacker (Wettsaasen). 3785 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Charlotte PICARD. 760 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 1 records from University of Nebraska State Museum Birds Collection. 14 records from Mollusques continentaux de France - LNE base de données Mulette perlière déclinaison régionale du PNA. 5 records from University of California Santa Barbara Invertebrate Zoology Collection. 151 records from Culture Collection of Microalgae and Zygnematophyceae Collection Hamburg (MZCH-SVCK). 92 records from Wiesen in der Grünen Mitte. 76 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Neue Milbenarten aus Kärnten. 1189 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Observations naturalistes d'Hervé BRUSTEL. 1091 records from Entomology Collection at the Natural History Museum of Utah. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 867 records from Étude des invertébrés sur les sites Natura 2000 de l'estuaire de la Gironde - Inventaire lépidoptère et odonate. 100 records from Australian National Insect Collection. 6 records from ALCB - Herbário Alexandre Leal Costa. 9 records from Herbarium specimens of Limoges university (LIMO). 3190 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 53 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Pierre DUCAMP. 39 records from Schulteich Freie Waldorfschule Darmstadt. 177 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de GOUDIABY Akaren (SAPROX). 10 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Manon DESPEAUX. 6 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 96 records from Observatoire des sites majeurs - LEYRE - Inventaire et suivi Loutre d'Europe. 1800 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 51694 records from Slovenian Fungal Database - Boletus informaticus. 1582 records from Freshwater fish records via iRecord. 1253 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 1153 records from Inventaires et suivis programme Lagunes mené par le Département des Landes - Ensemble des données Odonates. 97 records from The Diptera Site. 1140 records from Total foraminifera counts of multinet M36/6_MSN1196. 30767 records from National Dormouse Database (NDD). 127 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de TEISSEDRE BERTRAND. 1422 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 89 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste PARISOT FRANCK provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 4149 records from Temporal evolution of zooplankton by WP2 net in the Northwestern Mediterranean Sea, Villefranche-sur-mer 2004-2010.. 42 records from ONCFS Réseau Ours brun - Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 12 records from Art´n Vielfalt im Kinderwald. 40 records from Inventaire du site Natura 2000 FR7401107 "Landes des Monédières" - Inventaire chiroptères. 48 records from Identity of bryozoan species described by Jullien & Calvet from the Bay of Biscay historically attributed to Smittia. 57 records from Observation of the cultivation of oyster larvae in the Spuikom Oostende in 1964. 11 records from Benthic macrofauna abundance of sediment core 13077-093. 182791 records from Phase 2 Lowland Grassland Survey of Wales. 3608 records from hymenoptera. 3 records from Données naturalistes de PATOUX jean pierre. 189 records from Naturalis Biodiversity Center (NL) - Crustacea. 16055 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Matthieu TAILLADE. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2010 (réseau Ongulés sauvages ONCFS-FNC-FDC). 95 records from Birdrace-Buteo1_DO-Dortmund. 350 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 1362903 records from CLICNAT- Base de données naturaliste picarde - CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 11029 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 121 records from Foraminifera abundance of sediment core IN68-28. 32 records from Royal Museum of Central Africa - True Fruit Flies (Diptera, Tephritidae) of the Afrotropical Region (ENBI wp13). 477 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Aurélie CHEVILLON. 47783 records from Geneva Herbarium – General Collection (G). 148 records from Benthic foraminifera abundance of Hole 80-549A. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 14 records from Dimitri Multeau Loir-et-Cher Nature. 98 records from Regroupement d'études et inventaires - Données opportunistes sur les odonates. 348 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 67 records from Plan de gestion 2019 - 2023 de la Réserve Naturelle Régionale de l’Étang de Chourroumillas (64) mené par le CEN Nouvelle-Aquitaine - Observations d'odonates (imagos) réalisées par le CEN Aquitaine selon le protocole STERF. 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 16877 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données Entomologiques A. HORELLOU 1988-2018. 285 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 245 records from Ecology, phenology and wintering behavior of Anatidae in the wetlands of Souk-Ahras (north-eastern Algeria). 1777 records from ATBI Parc national du Mercantour / Parco naturale Alpi Marittime - EXPLOR'NATURE 2018, inventaire biologique de la commune de Sospel. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 208 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 456 records from EDIT - ATBI in Gemer area (Slovakia). 320 records from Global compendium of Aedes albopictus occurrence. 325 records from Mollusques continentaux de France - Inventaire malacologique de la RNR des Marais de Stors. 11111 records from Atlas communaux de la biodiversité du Parc Naturel Régional des Landes de Gascogne 2014-2020 - Inventaire de la flore du PNRLG 2014 (Landes et Gironde). 431236 records from Natural History Museum (London) Collection Specimens. 2 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 304 records from Ried und Sand - Artenvielfalt durch Beweidung. 152 records from AKG-Gelände (Bensheim). 115 records from Diagnostic écologique et élaboration d'une notice de gestion (prairies humides et calcaires) sur la commune de Monflanquin (47) menés entre 2017 et 2022 par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 168 records from Occurrence of mammalia relicts at site Grotte Scladina. 5977 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 2718 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 115 records from Données de présence collectées sur les écrevisses. 6 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 80 records from Förderzentrum Schmölln. 9 records from Suivi ornithologique du Bassin de stockage de Balanos - Données ornithologiques du bassin de stockage de Balanos. 1432 records from Collection botanique Jaubert et Saul (BOUM). 210 records from Lebensraum Gesamtschule (Langerwehe). 14 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Kathy FOOT. 367 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 4 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Jean-Yves BOUTET. 2508 records from Données des collections du MNHN - Données des collections d'algues du MNHN. 1 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 73 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Jarry Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 939 records from Les Coléoptères Silphidés du département du Loiret. 760 records from Total foraminifera counts of multinet M21/2_MSN648. 289 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 1 records from Plan de gestion 2016 - 2020 du site des Berges de l'Arlas et du Luy de Béarn (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 1443 records from Appui technique et scientifique aux réserves naturelles (nationales et régionales) - Données invertébrés RNN CEN L-R. 6 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 137 (N.S) n° 30 (1), 2002 - Données faune. 6400 records from Regroupement d'études et inventaires - Regroupement de données Rhopalocères. 15482 records from Marine sediment Raw sequence reads. 2 records from Occurrence of mammalia relicts at site Igstadt I. 307273 records from Activité générale du bureau d'étude BIOTOPE (1994 - 2013) - Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 17 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de HENDOUX Frédéric. 14 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 868 records from Danielsberg (Mölltal, Kärnten). 255 records from Parc éolien des Portes de la Brenne - Données-SINP-Flore. 13000 records from SILENE-FAUNE-PACA - LPO_PACA_2017_12_18. 793 records from Sphaeriid clams. 13177 records from Harbour seals GPS telemetry in Baie de Somme. 190 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 661 records from Targeting a portion of central European spider diversity for permanent preservation. 13 records from New species and additional records of Lomechusini from the Palaearctic region, primarily from China (Coleoptera: Staphylinidae: Aleocharinae). 1014 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 2006 - 2010 Coordonnées GPS Lambert 93. 727 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Faisan commun 2009 - 2013 Coordonnées GPS Lambert 93. 2024 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 20938466 records from INPN - Données flore des CBN agrégées par la FCBN. 119 records from Notes à la flore de Corse, XXV. 343 records from Foreign plant germplasm collections in Ghana. 575481 records from Forestry Inventory 2010. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 1 records from Seabirds of the Southern and South Indian Ocean. 88489 records from Observatoire Pelagis boat surveys 2003-2021. 18 records from Meiofauna abundance in sediment core 12930-036. 170 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 1 records from Plan de gestion 2016 - 2020 du site des Landes humides de Mouguerre (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 313 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 2783 records from Collection Pisces SMF. 1809 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 78 records from (Figure 2) Distribution chart of dinoflagellate cysts of Cretaceous age from ODP Hole 103-638C. 1 records from MEXU/Tipos de plantas vasculares. 2036 records from Données du Parc Naturel Régional du Perche - Données Odonates du Parc Naturel Régional du Perche. 872 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive musicienne 2007 - 2011 Coordonnées GPS Lambert 93. 8665 records from Abundances and biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Oir river (France). 1553 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 2 records from Animation du Document d’objectifs du site Natura 2000 FR7200799 - Carrières de Castelculier (47) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Nouvelle-Aquitaine. 210 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 242 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - EPTBSGL_ANSE_ARCOT_2019. 462 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Plan de gestion 2019 - 2023 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par la RNG Saucats - La Brède. 489 records from Données naturalistes de ROMET Nicolas. 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 1010 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Daniel PAVON. 1 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 1140 records from Total foraminifera counts of multinet M21/1_MSN606. 38 records from Réseau Loup - Lynx ONCFS - Lynx 2002 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 912 records from Total foraminifera counts of multinet M6/7_MSN116. 999 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pigeon ramier 2007 - 2011 Coordonnées GPS Lambert 93. 38 records from ONCFS Réseau Ours brun - Ours 2007 présence Régulière Mailles_10km_LAEA Réseau Ours brun ONCFS. 194 records from Lindau im Bodensee. 58640 records from Herbarium Willing at Herbarium Berolinense, Berlin (B). 1628 records from KTU Pinophyta. 4 records from NCSM Mammalogy Collection. 3 records from Mise en oeuvre des mesures compensatoires à l'aménagement du parc photovoltaïque d'Hourtin - Données opportunistes. 429 records from Crustacés Branchiopodes Phyllopodes de France. 42 records from Inventaire des Lépidoptères Rhopalocères et Zygènes de France métropolitaine - Données de Rhône-Alpes transmises par Pascal Peyrache.. 1 records from HCF herbarium - Universidade Tecnológica Federal do Paraná - Campus Campo Mourão - Herbário Virtual REFLORA. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Elisabeth MERCADER. 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 37 records from A summary of benthic studies in the sluice dock of Ostend during 1976-1981. 9072 records from Chondrichthyans Of Ireland. 5 records from Fledermäuse u. nachtaktive Insekten. 359 records from Mollusques continentaux de France - Inventaire malacologique du site Natura 2000 FR9301537 de la Montagne de Lure (2002, ONF/MNHN). 870 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 9 records from tranfert des activités ferrovaires du site de Nantes-Etat vers le site de Nantes-Blottereau - Inventaire d’espèces végétales protégés et/ou patrimoniales - Point. 1901 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Syndicat_Mixte_d'Aménagement_de_la_Vallée_de_la_Durance_2017_12_18. 109414 records from Bryophyte data for Great Britain and Ireland from the British Bryological Society held by BRC: data compiled post-Atlas. 798 records from Plan régional d'actions en faveur des odonates (PRAO) : 3ème phase (2017 - 2018) menée par le CEN Aquitaine - Observations d'odonates réalisées lors de journées de prospections animées par la LPO Aquitaine. 1140 records from Total foraminifera counts of multinet M21/1_MSN604. 2889 records from Heleomyzid Recording Scheme - data verified via iRecord. 41 records from Etude préalable au plan de gestion des lagunes d'Hourtin pour la protection des sites à leucorrhines menée entre 2015 et 2019 par le CEN Aquitaine - Observations faunistiques (suivi par point d'écoute) réalisées par le CEN Aquitaine. 25 records from The Purdue Entomological Research Collection. 44 records from Distribution des grenouilles vertes (Pelophylax spp.) en région méditerranéenne - Répartition Pelophylax spp. en 2012 pour l'évaluation de l'état de conservation (article 17 de la Directive Habitats). 6 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" de la tourbière de Maoucout (SAINT-MICHEL-ESCALUS). 459 records from Données biodiversité projet éolien des Navarros. 1354 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" de Gaouchey et de Garlande (LUXEY). 2560 records from Upper Silesian Museum, Bird Observations. 171 records from Plan de gestion 2019 - 2023 de la Réserve Naturelle Régionale de l’Étang de Chourroumillas (64) mené par le CEN Nouvelle-Aquitaine - Observations d'odonates (imagos) réalisées par le CEN Nouvelle-Aquitaine selon le protocole STELI. 11 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 15 records from Regenwasserabfangsbecken (Erlenbach). 12496 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 1657 records from Inventaire de la Réserve Naturelle de l'étang de Cousseau - Inventaire et suivi Rhopalocères. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 822 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 1449 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Philippe GOURDAIN (ANVL). 53 records from Plan de gestion 2017 - 2021 du site des Landes humides de Mazerolles (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 272 records from BIRDRACE Niederlausitz-Team. 539 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - L'Amateur de Papillons. 6 records from Revisions to the faunas of Andrena of the Iberian Peninsula and Morocco with the descriptions of four new species (Hymenoptera: Andrenidae). 859275 records from The CPR Survey. 21319 records from Données Faune Base SIRFF - FNE Centre-Val de Loire - Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2015. 28 records from Plan de gestion 2019 - 2023 du Lac de La Prade (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 2 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Damien TROQUEREAU. 19 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 41 records from UFRN-Fungos - Herbário UFRN - Fungos. 6830 records from Epibenthos and demersal fish monitoring in function of dredge disposal monitoring in the Belgian part of the North Sea. 111 records from Shannon Index and species richness for herbivores. 962 records from Appui technique et scientifique aux réserves naturelles (nationales et régionales) - Données invertébrés RNN. 1001 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pigeon ramier 2008 - 2012 Coordonnées GPS Lambert 93. 217 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 2504 records from Inventaires chiroptérologiques pour l'amélioration de la connaissance de la biodiversité et des habitats des chauves-souris - Données invertébrés GCMP. 2 records from Animation du plan de gestion de l'étang de Langouarde - Suivis amphibiens. 13 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Mollusques - Inventaire non standardisé - FRAPNA74 - 24HNAT. 5371 records from CLICNAT- Base de données naturaliste picarde - Données de terrain du CPIE des Pays de l'Aisne. 713 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Decroo Jean-Paul provenant de la base de donnée du SINP Île-de-France CETTIA. 377 records from SILENE-FAUNE-PACA - CG04_2017_12_18. 52 records from GenLink - Genetic diversity of Trifolium repens. 719 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 282 records from Faberpark (Nürnberg/Stein). 912 records from Total foraminifera counts of multinet M21/1_MSN611. 45 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 11 records from Collection Ephemeroptera - SMF. 524 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 8022 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 290 records from Denver Museum of Nature & Science - Entomology. 3 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Marc GAGNE. 65 records from Projet du parc éolien de la Voie des Prêtres 2 - Liste de l'avifaune recensée en période de reproduction en 2010 et 2011. 16150 records from Database for alien invasive plants occurrences in Germany. 113 records from Tornoer Teich. 69 records from Birdrace-NAJU_Aspach-Rems/Murr. 150 records from Programme les sentinelles du climat - effets du changement climatique sur la biodiversité en région Nouvelle-Aquitaine - Observations d'odonates réalisées par la Réserve naturelle nationale de l'Étang Noir selon le protocole STELI adapté pour le programme. 1 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 39 records from Collection of Hymenoptera. 60 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Sarouille Romain provenant de la base de donnée du SINP Île-de-France CETTIA. 1128 records from pflanzendiversitaet_2008_sch_alb_hai_aktualisiert. 31 records from Nationalpark Harz Schul-AG Braunlage. 677 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 1 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 1 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Gérard LALANDE. 18 records from AMF Colonization VIP 2008 Rillig. 23 records from AKG-Gelände in Bensheim. 139 records from Occurrence of mammalia relicts at site Velika Pecina. 364 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Les mollusques terrestres de la faune de Corse : Mission 2019. Muséum national d'Histoire naturelle, Paris et DREAL Corse. 38 records from Was lebt in der Brutzwiese?. 636 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 142 records from Sperm morphology of 264 songbird species. 211 records from Centrale photovoltaïque de Lux - Données faune/flore CAEI. 47 records from Stigmella stettinensis (Nepticulidae) specimen data. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Josselin DUFAY. 96640 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 19 records from Michigan State University Herbarium Lichens. 86 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pierre-Alexis RAULT. 2 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Nicolas SECONDAT. 5 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 28 records from Réseau Loup - Lynx ONCFS - Lynx 2000 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 3980 records from Dark ocean microbial diversity. 28 records from Observations of Protohydra leuckarti within Europe and beyond. 49 records from VFD-H.: Rheingau: Bärstadt. 429 records from EDP Foz Tua Reptiles - Ecological Monitoring Program [2011-2017]. 1281 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Avifaune Lande sèches. 1343 records from Plymouth sound dataset. Soft sediment macrobenthos from the Plymouth Sound from 1995. 1006 records from Inventaire de la RNN du Marais d'Orx - Inventaire et suivi Rhopalocères – Protocole STERF. 1029 records from Pollen profile from Achenhang. 113 records from Données Orthoptères opportunistes Osmunda 2015-2017. 509 records from Programmes d'Atlas de la biodiversité communale (ABC) - Atlas de la Biodiversité Communale sur les communes de Montmaurin, Lespugue et Blajan - Haute-Garonne - Données du CEN MP. 12 records from Kinderwald Hannover. 1 records from Archaeal 23S Ribosomal RNA RefSeq Targeted Loci Project. 338 records from Unser Schulgelände. 401 records from Carabidae of Poland. 722 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette des champs 2012 - 2016 Coordonnées GPS Lambert 93. 876 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive musicienne 2006 - 2010 Coordonnées GPS Lambert 93. 85 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Mikaël PAILLET. 66 records from Suivis faunistiques du site du Moulin de la Ville - Suivi Amphibien - POPAmphibien. 486 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 1418 records from University of Michigan Museum of Zoology, Division of Insects. 157817 records from Programme CarNET B (Cartographie Nationale des Enjeux Territorialisés de Biodiversité Remarquable) - Carnet B Centre - lot 2012. 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 6 records from Three new species of Entomobrya from Poland (Collembola, Entomobryidae). 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 67 records from Benthic foraminifera abundance of Hole 80-550. 2803 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Pie verte bio provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 12 records from Collection Ichthyologie - SNSD. 58 records from Occurrence of mammalia relicts at site l´Abri de Rhodes II. 806 records from Seasearch Pink Sea Fan, Eunicella verrucosa, Survey. 3120 records from Pollen record of sediment core Bokanjacko Blato 1. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 692 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2006 - 2010 Coordonnées GPS Lambert 93. 36 records from SILENE-FAUNE-PACA - BIOMEO_2017_12_18. 87 records from Distribution of aquatic beetles from the east of Morocco (Coleoptera, Polyphaga). 59 records from Inventaires sur le réseau Aquitaine Nature du PNR Périgord-Limousin - Inventaire sur le site de la Pierre levée. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain). 4 records from The reptile type specimens preserved in the Museo Nacional de Ciencias Naturales (CSIC) of Madrid, Spain. 121 records from Étude des invertébrés sur les sites Natura 2000 de l'estuaire de la Gironde - Inventaire coléoptère. 300 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste FAUCHER Alexandre provenant de la base de donnée du SINP Île-de-France CETTIA. 661 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 17 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe). 18416 records from Inventaire de la flore de Charente-Maritime 2012-2020 - Inventaire de la flore de Charente-Maritime 2015. 122 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive littorne 2012 - 2016 Coordonnées GPS Lambert 93. 207 records from Plan de gestion 2012 - 2016 de la Réserve Naturelle Régionale d'Errota Handia (64) mené par le CEN Aquitaine - Observations faunistiques (suivi par piège photographique) réalisées par le CEN Aquitaine. 49 records from Fungi collection of Jyväskylä University Museum. 4 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 1047 records from NMNH Paleobiology Specimen Records (USNM). 104 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Conventionnement de la commune de Chepnier. 15 records from DMNS Bird Collection (Arctos). 182923 records from Temporal variation in pesticide biodegradation. 34424 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 38 records from Plan de gestion 2004 - 2008 du site de l’Étang de Chourroumillas (64) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par l'association "Le Paon du Jour". 384 records from Collection ornithologique A. Maës. 456 records from Ferme pilote d'éoliennes flottantes de Groix & Belle-Ile et son raccordement au Réseau Public de Transport d'Electricité - Campagne d’investigations ichtyofaune – Ferme pilote de Groix & Belle-Ile. 118 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Observation des insectes sur le territoire de la Métropole Rouen Normandie. 9 records from Phylogenomic re-evaluation of Triaenonychoidea (Opiliones: Laniatores), and systematics of Triaenonychidae, including new families, genera and species. 171 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 295 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Anjuerer Jack provenant de la base de donnée du SINP Île-de-France CETTIA. 498 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Swift Olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 173 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive littorne 2003 - 2007 Coordonnées GPS Lambert 93. 9 records from Données espèces - Expertise IQE 35. 7 records from Projet de parc éolien de la Croix Guingal, sur la commune de Derval (44 590) - Croix Guingal - chiro - transit printanier 2014. 6072 records from The Fungal Collection at the Botanische Staatssammlung München. 1030 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 1996 - 2000 Coordonnées GPS Lambert 93. 623 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 151 (N.S) n°44 (2-3), 2016 - Données faune. 226 records from Phanerogamic Botanical Collections (S). 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 4 records from Review of the genera Pristocera Klug and Pristepyris Kieffer (Hymenoptera Bethylidae, Pristocerinae) of Russia and adjacent territories. 46 records from An der Ohm, (Wettsaasen). 42 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de DUMAS Yann. 2 records from Anisops sardeus Herrich-Schaeffer, 1849: first records from Hungary (Heteroptera: Notonectidae). 185 records from Elaboration du DOCOB du site Natura 2000 ‘Réseau hydrographique des affluents de la Midouze’ (FR7200722) - Inventaire des odonates d'intérêt communautaire. 1 records from Manx Basking Shark Watch 2017-2018 (aggregated per 1-degree cell). 7 records from Projet de centrale photovoltaïque au sol de la ZA de l'Etang Bertrand - Amphibiens - Inventaire non standardisé. 2116 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données de la collection de Hubert Piguet - Famille des Elateridae. 244 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de BRUGEROLLES Yvan. 47 records from Projets de suivis faunes association Environat - suivi odonates environat. 4235 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 9 records from Projet Courlis cendré et avifaune associée - Inventaire Avifaune. 1 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Avifaune Lande sèches. 977 records from Gurgltal (Tarrenz). 133 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Duret Bertrand provenant de la base de donnée du SINP Île-de-France CETTIA. 259 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette lulu 2009 - 2013 Coordonnées GPS Lambert 93. 1929 records from Clémence Lortet herbarium. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 1088 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 9 records from Israel Sea Turtle Tracking Project 2008: Loggerhead & Green Turtles (aggregated per 1-degree cell). 12 records from Naturschutzgebiet Swistbachaue (Eckendorf). 25 records from University of Cincinnati, Margaret H. Fulford Herbarium - Lichens. 86 records from Jurica-Suchy Nature Museum at Benedictine University Fossil Specimens (Arctos). 3253 records from Hemiptera: Auchenorrhyncha: Records for Kent. 98 records from Projet éolien de Berceronne - Données brutes Chiroptères. 1 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 1 records from Pilosella hoppeana subsp. sicula Di Grist., Gottschl. & Raimondo (Asteraceae), a new endemic subspecies from Sicily (Italy). 804 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Danten Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 1751 records from Marine Turtles. 59780 records from Flora d'Andorra. 7 records from Suivi et inventaire de la réserve naturelle de Saucats - La Brède - Données récoltées dans le cadre du suivi de la réserve. 349 records from The InBIO Barcoding Initiative Database: Lacewings (Neuroptera) 02. 35 records from Animation technique des sites Natura 2000 ‘Barthes de l'Adour’ - Suivis rapaces 2019 - Site Natura 2000 des Barthes de l'Adour. 786 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle des bois 2011 - 2015 Coordonnées GPS Lambert 93. 760 records from Total foraminifera counts of multinet M21/2_MSN650. 467 records from Inventaire Odonates-Rhopalocères 1999-2002 du PNRLG - Données rhopalocères. 307 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 743 records from SILENE-FAUNE-PACA - Thibaut_LACOMBE_2017_12_18. 10 records from Sediment properties of core PLG95B_06BOXG. 3106 records from Standing Waters Database - Scotland. 120 records from Abundance of living benthic foraminifera in sediment core CD86_08_BC5. 72 records from Etude Chiroptères du domaine de Peyssac - Etude Chiroptères de Peyssac. 463 records from Foraminifera abundance of sediment core IN68-9. 3852 records from Données faune ZNIEFF de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS. 155 records from Small mammal species list 08. 1 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 1100 records from MijnVISmaat - Exotic fish occurrences in Belgium. 4 records from University of Guelph Insect Collection (DEBU). 80 records from 59 - Beau Gui Flore. 760 records from Plasm bearing foraminifera counts of multinet M21/2_MSN629. 50 records from Junge Heide, Radebeul/Dresden. 102 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" de l'étang du Houa (SAINT-MICHEL-ESCALUS). 112 records from Projet éolien de Saint-Barbant - Flore. 229 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de LEENKNEGT Virginie. 1 records from Overview of bat species reported in Albania with the first country records for eight species. 457 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Rossi Stéphane provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Herbarium Senckenbergianum (FR) - Protista. 30 records from Plan de gestion 2015-2020 de la tourbière de Passeben - Inventaire et suivi des libellules – Protocole STELI. 4 records from 1ère phase d'animation (2017 - 2020) des Documents d’objectifs des sites Natura 2000 FR7200665 "Coteaux calcaires de Proissans, Sainte-Nathalène et Saint-Vincent-le-Paluel", FR7200672 "Coteaux calcaires du Causse de Daglan et de la Vallée du Céou" et FR7200676 "Coteaux calcaires de Borrèze" (24) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 1 records from The mature larva and pupa of Tychius subsulcatus Tournier, 1847 (Coleoptera, Curculionidae), with comments on its biology and phylogenetic relationships. 6218 records from Records from the RHS insect reference collection. 68775 records from Données de la plateforme régionale SINP DREAL Bourgogne - Données de l'Observatoire de la Faune de Bourgogne. 265 records from Mollusques continentaux de France - Les mollusques terrestres de la faune de Corse : Mission 1996 de Theo RIPKEN.. 10 records from Projet de centrale photovoltaïque au sol de la ZA de l'Etang Bertrand - Chauves-souris - Points d'écoute au sol. 256 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Perdrix rouge 2009 - 2013 Coordonnées GPS Lambert 93. 18 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 20 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Jean-Patrick Le Duc. 1 records from Occurrence of mammalia relicts at site Conturines Höhle. 8 records from Renaturation du ruisseau de l'Ousse des Bois - Données de la pêche de sauvetage. 267 records from Turbellaria from mudflats in the Zwin nature reserve (1983-1984). 212 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 199 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette lulu 1996 - 2000 Coordonnées GPS Lambert 93. 5810 records from Grassland cartography SICONA, Recorder-Lux database. 13 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 1077 records from Allan Herbarium (CHR). 130 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 59 records from Données opportunistes collectées par les agents du Département des Landes. 531 records from Artemia (Crustacea, Branchiopoda, Anostraca) cyst bank (IATS-CSIC). 44 records from Etude d'aménagement foncier du bassin d'alimentation du captage du Vivier - Périmètre 1 - Données Lépidoptères et Odonates - Vivier 1. 8 records from Review of the genus Typhloiulus Latzel, 1884 in the Dinaric region, with a description of four new species and the first description of the male of Typhloiulus insularis Strasser, 1938 (Diplopoda: Julida: Julidae). 13236 records from Données CEN L-R RHOMEO. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 11 records from Plan de gestion 2013 - 2018 du site du coteau de Lembeye (64) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 71 records from Cercle des mycologues de Montréal Fungarium (CMMF). 6 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 497212 records from CRBPO : STOC, Baguage. 33 records from Projet de parc solaire Figanieres - Insectes - Inventaire non protocolé. 117 records from Inventaire du site Pierre Fabre de Cahors. 3 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Séverine VITRAT. 1036 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 143 records from Banco de semillas Jardín botánico de Cartagena "Guillermo Piñeres". 232 records from Vorderer Tiergarten (Dessau). 6 records from WIKTROP - Weed Identification and Knowledge in the Tropical and Mediterranean areas. 1140 records from RU-BIRDS.RU, Birds observations database from Russia and neighboring regions. Zoological Museum of M.V. Lomonosov Moscow State University.. 55 records from Seeufer ehem. BUGA-Gelände. 1597 records from Meetnetten.be - Egg counts for butterflies in Flanders, Belgium. 1 records from Synthèse de la Répartition des populations de mouflon corse en 2011 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1189 records from kerkyra. 50159 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 69 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 336 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 44074 records from NDFF Butterfly Data. 311 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Friches urbaines de Marseille. 53 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 3752 records from Inventaire et évaluation des pelouses calcicoles du Parc Naturel Régional du Marais Poitevin 2017-2018 - Inventaire des pelouses calcicoles du PNR du Marais Poitevin 2017. 9239 records from Chrysomelidae beetle data from iRecord. 162 records from Abundance of living benthic foraminifera in sediment core CD86_05_BC5. 4 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 28 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Chiro Pioussay. 5 records from The Apseudomorpha (Crustacea: Tanaidacea) of the Gulf of Cadiz and Horseshoe Continental Rise (NE Atlantic): A taxonomic review with new records, species, and ecological data. 29 records from Brenz (Heidenheim). 25 records from Plan de gestion 2016 - 2020 du site du Coteau de Savoye (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 18 records from Parc Eolien Les 7 Domaines - Inventaire des Busards cendrés nicheurs en 2014.. 790 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2009 - 2013 Coordonnées GPS Lambert 93. 59 records from Mica - Muskrat, Raccoon and Coypu occurrences collected by ITAW in Germany. 1216 records from Total foraminifera counts of multinet M21/6_MSN785. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 262 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de William BATIFOIX. 286 records from Records of Invasive Non Native Species held on the Cofnod database. 330 records from Benthic macrofauna abundance of sediment core 13200-004. 53 records from BIRDRACE Taubenhaucher. 1114 records from Benthic foraminifera of sediment core M25/4-KL13. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 31 records from Kurler Busch (Scharnhorst). 111 records from Birdrace-Uhulogen-Lippe. 35 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 11 records from Occurrence of mammalia relicts at site Buchenloch. 5 records from Plan de gestion 2019 - 2023 du site des Grottes de Sare (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 292 records from BIRDRACE Havelland. 1 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 39 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Nathan HAUQUIN. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 102 records from Otter survey of Ireland 2004 & 2005. 27719 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Grosso Eric provenant de la base de donnée du SINP Île-de-France CETTIA. 8307 records from POPA- Fisheries Observer Program of the Azores: Tuna species caught in the Azores tuna fishery from 1998 to 2013. 30 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 120 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 449 records from Suivi de l'évolution des populations - Regroupement de données opportunistes. 133688 records from Suivi Temporel des Rhopalocères de France (STERF). 571 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - MalaCo, Journal de Malacologie continentale [2005-]. 6 records from Comparative description of the Mediterranean erigonine spider Diplocephalus guidoi n. sp. (Araneae, Linyphiidae). 3891 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Données d'occurrence d'espèces contenues dans l'ouvrage de Simon, Les Arachnides de France (tome 6). 59 records from (Fig. 2) Abundance of Uvigerina pygmaea in sediment core MD95-2040. 1140 records from Total foraminifera counts of multinet POS247/2_MSN1386. 1230 records from Projet BiodiverCité - Données protocolées Odonates. 23 records from Landwehrbach. 105 records from Projet BiodiverCité - Données opportunistes de Frédéric Revers récoltées lors des prospections terrains. 31 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Maxime COSSON. 14 records from Mammals Specimens. 527 records from SIM-XII-XIII Jornadas Micológicas El Ilustre Minero. 40 records from Alien Species in Poland - Plants. 11 records from Inventaires et suivis effectués sur les retenues collinaires de l'Institution Adour - Inventaire sur la retenue collinaire de Renung. 27 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Philippe VEILLON. 305 records from Nematode densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 402 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de VINCENT Alexis (SAPROX). 53 records from Weidegut Rechab. 4469 records from National System of Protected Areas in Poland - Plants. 53 records from Condon Fossil Collection - Oregon Museum of Natural and Cultural History. 1 records from Glasgow Museums BRC: Chrysomelidae. 767 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2011 - 2015 Coordonnées GPS Lambert 93. 56 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire Espace Naturel Sensible de l'Etang de Gaube. 27 records from Projet de parc éolien en mer des îles d'Yeu et de Noirmoutier - demande de dérogation espèces protégées - Mammifères marins GT - Inventaire non protocolé. 47 records from Occurrence of mammalia relicts at site Erdhöhle. 1652 records from Bryophyte diversity in grassland. 374 records from (Figure 3) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 103-641A. 897 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 14 records from Suivis télémétriques de phoques gris par Océanopolis et l'Université de La Rochelle - Observations issues des suivis Argos des phoques gris en Atlantique et Manche Mer du Nord. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de CARON Nicolas. 43 records from Unexpected diversity of the genus Collarina Jullien, 1886 (Bryozoa, Cheilostomatida) in the NE Atlantic-Mediterranean region: new species and reappraisal of C. balzaci (Audouin, 1826) and C. fayalensis Harmelin, 1978. 2631 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 323 records from SMNS Herpetologie. 316 records from Underwater fish visual census in the Azores from 1997 to 2015. 106 records from Occurrence of mammalia relicts at site Geißenklösterle. 5037 records from Pollen analysis of sediment profile SI0 from Siethener See. 371 records from Plan de gestion multi-site 2018 - 2022 des étangs de Mios (33) mené par le CEN Nouvelle-Aquitaine - Observations d'odonates (suivi STELI) réalisées par le CEN Aquitaine. 133 records from Sizing Ocean Giants. 448 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Etourneau sansonnet 2006 - 2010 Coordonnées GPS Lambert 93. 7 records from Projet de parc éolien de la Croix Guingal, sur la commune de Derval (44 590) - Croix Guingal - Chiro - parturition 2014. 622 records from Inventaires Odonatologiques de sites ENS du Pôle Nature de Vitrezay (St Sorlin de Conac) et de St Clément des baleines - Liste odonates 2 sites ENS Charente-Maritime. 7 records from Amphibia and Reptilia (Luomus). 475 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 29523 records from Données du Parc national des Cévennes - Inventaire et suivis d'espèces dans le Parc national des Cévennes. 933242 records from SEWBReC Birds (South East Wales). 1 records from Plan de gestion 2017 - 2021 du site «Coteaux de Brungidour et des Foncillières» (24) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par Vya Natura (étude de l'avifaune nicheuse). 168 records from Die Teiche im Britzer Garten. 1 records from Laophontodes typicus T. Scott (Copepoda, Harpacticoida, Laophontodinae) - discovering a species complex by morphology. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 103 records from Collection Echinodermata SMF. 4765 records from MfN - Fossil vertebrates IV. 160 records from AIS Wildtype Populations of Arabidopsis. 212 records from Bearded Tit National Survey in Britain 2002. 289 records from Planktic foraminifera abundance of Hole 42-372. 1970 records from Dipterists Forum: Field Week 1981 (Kent). 225 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 625 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de Corse par Canard A., Rollard C., Villepoux O.. 371 records from Projet éolien - Oiseaux - Inventaire non protocolé. 1 records from Description of a new Gibbaranea (Araneae: Araneidae) from the Western Mediterranean. 7757572 records from Pl@ntNet automatically identified occurrences. 19339 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes opportunistes de Sandy Barberis. 97 records from Base BOMBINA du Parc Naturel régional Lorraine - Amphibiens filet/Marbotte-Ronval 2013. 119302 records from Amphibiens et Reptiles de France (Enquête 2). 2126 records from Dolichopodidae of Portugal - dataset 2009-2018. 10167 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Noctuoidea de France métropolitaine. 34 records from Expertise dans le cadre d'une sollicitation liée à une étude d'impact - Données GSM Carrière Espeyran. 160 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Provost Romain provenant de la base de donnée du SINP Île-de-France CETTIA. 14 records from Contribution à la connaissance des Orthoptères – Locusta - Données opportunistes de Benoit DUHAZE. 11 records from Rencontre annuelle des hétéroptéristes organisée en 2020 par l'association Zicrona dans les Landes - Observations d'hétéroptères (inventaire) réalisées par l'association Zicrona. 1386 records from Regroupement d'études et inventaires - Données opportunistes. 19 records from Ring ouzel national sample survey in the UK in 1999. 84517 records from Phenology and biological traits of migrating salmon (Salmo salar) sampled by trapping in the Scorff river (France).. 255 records from Elaboration du DOCOB du site Natura 2000 ’Réseau hydrographique du Midou et du Ludon’ (FR7200806) - Inventaire et regroupement de données Natura 2000. 12712 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 13 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 1997. 266 records from PARC PHOTOVOLTAIQUE à RIANS - Flore. 638413 records from Inventaire de la flore d'Alsace - Données de la flore d’Alsace (SBA). 131 records from BIRDRACE Brut. 26 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Mammifères - Inventaire non standardisé - FRAPNA74 - 24HNAT. 77 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi naturaliste du Parc du Peuple de l'Herbe. 72 records from Birdrace-Buteo2DO-Dortmund. 846 records from PAMP-tracheo: Vascular plants in La Demanda and Cameros mountain ranges (La Rioja, Spain). PhD project, L.M. Medrano. 56 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 1712 records from Plateforme AUVERGNE-DREAL Auvergne - DREAL Auvergne - Insectes - 2015. 26185 records from Données de Mammifères issues de Baznat. Midi-Pyrénées - Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 165 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pigeon colombin 2012 - 2016 Coordonnées GPS Lambert 93. 2 records from Suivi Cistude d'Europe du Bassin de stockage de Balanos - Données Cistude d'Europe du Bassin de stockage de Balanos. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 3930 records from Regroupement d'études et inventaires - Données opportunistes fortuites sur les rhopalocères récoltées lors des prospections terrains. 3 records from Plan de gestion Les Mattes de Paladon et Marais de Neyran - Suivi orthoptères. 359 records from Pöhlberg bei Annaberg. 203 records from NHMD Ornithology Collection. 32 records from "Wildnis erleben" - "Vielfalt erlebbar machen" - Botanischer Garten u.Chrimmitschauer Wald. 1 records from Revision of Pseudexogone Augener, 1922 (Annelida, Polychaeta, Syllidae), and its transfer to Pilargidae. 83656 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 423 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Caille des blés 2008 - 2012 Coordonnées GPS Lambert 93. 44 records from ONCFS Réseau Ours brun - Ours 2010 présence Régulière Mailles 10km LAEA Réseau Ours brun ONCFS. 25 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 138 (N.S) n° 31 (1), 2003 - Données faune. 4229 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Loïc SALAUN. 1 records from Mollusk Collection of Yokosuka City Museum. 9277 records from MfN - Fossil plants (Paleophytic). 913 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle turque 2003 - 2007 Coordonnées GPS Lambert 93. 2172 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 395 records from Inventaires et suivis sites compensation contournement sur la commune de DAX - Suivi Odonates. 1446621 records from Flore Franco-Belge. 166 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive littorne 2002 - 2006 Coordonnées GPS Lambert 93. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 131 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pigeon colombin 1996 - 2000 Coordonnées GPS Lambert 93. 3 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from Plan Aquitain d'Action Sonneur à ventre jaune - PRA Sonneur à ventre jaune - étude de répartition. 139 records from Les Terres Neuves 2 - Données brutes Flaure et Faune - Projet Terres Neuves 2. 338 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure SHF - Société Herpétologique de France provenant de la base de donnée du SINP Île-de-France CETTIA. 1716 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 2139 records from Collection Crustacea - ZMB. 47 records from Suivi et déplacement d'amphibiens pour la construction de la liaison RD656/RD119 et des carrefours associés (Amorce de la rocade Ouest d'Agen) - Suivi Amphibiens dans le cadre du chantier. 3523 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 21 records from Georgia Aquarium/DomSeTCO Leatherback's of Dominica (aggregated per 1-degree cell). 539 records from RHS Fuchsia Gall Mite (Aculops fuchsiae) monitoring. 131 records from Abundanz_Infloreszenzenschlupf_Pflanzenebene_2008. 266 records from Structure of waterbird assemblages in fragmented coastal wetlands of Northeastern Algeria. 86 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi des reptiles, insectes et flore de la forêt départementale de Rolleboise 2009. 23073 records from Freshwater fishes of Poland. 1 records from Parc éolien d'Argillières - hérpétofaune. 1140 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 196 records from MVZ Egg and Nest Collection (Arctos). 3 records from Differentiation among cave populations of the Eukoenenia spelaea species-complex (Arachnida: Palpigradi) in the southwestern Alps. 157 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pigeon colombin 2008 - 2012 Coordonnées GPS Lambert 93. 12 records from Enquête sur 3 mammifères protégés : le Muscardin, le Campagnol amphibie et la Crossope aquatique - Données mammifères Phase 1 récoltées par Nature Environnement 17. 1567791 records from CSIC-Real Jardín Botánico-Anthos. Sistema de Información de las Plantas de España. 24104 records from VIS - Non-native fish in Flanders, Belgium. 6 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Kevin CURTIL. 64 records from Kabelskebach (Kabelsketal, Saalkreis). 1 records from Plan de gestion 2019 - 2023 du site des Grottes de Sare (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 6 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Clément GRANCHER. 14 records from Canary Islands - OAG (aggregated per 1-degree cell). 10 records from An annotated type catalogue of the centipedes (Myriapoda: Chilopoda) held in the Zoological Museum Hamburg. 668 records from Freshwater Macrophyte Survey Data. 760 records from Plasm bearing foraminifera counts of multinet M21/2_MSN639. 500 records from Taxon occurrence data for the FungalRoot database. 9 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 1996. 148 records from Construction du village Alzheimer à Dax (40) - Inventaire de la Faune patrimoniale. 452 records from Gelände des IVL (Zeckern). 20 records from Life Vison d'Europe et espèces associées - Données de Vison d'Europe par piège-photo, capture ou indices indirects (empreintes...). 1356 records from Programme LIFE CROAA - Eradication de la Grenouille taureau : Piégeage. 217 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Anaelle WILLER. 4082 records from Meetnetten.be - Population counts for dragonflies in Flanders, Belgium. 2 records from E. C. Smith Herbarium (ACAD). 30 records from Plan de gestion 2013 - 2018 du site du Coteau de Peymourel (24) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 6 records from Planktic foraminifera abundance of Hole 42-372. 22126 records from Alterra (NL) - Entomofauna inventory in peat swamps. 146063 records from EBCC Atlas of European Breeding Birds. 959 records from Dead benthic foraminifera of surface sediments from the East Atlantic continental margin off Portugal (Table 5 & 7). 1857 records from Base BOMBINA du Parc Naturel régional Lorraine - Données diverses du Parc naturel régional de Lorraine. 344 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Caille des blés 2012 - 2016 Coordonnées GPS Lambert 93. 22 records from Occurrence of mammalia relicts at site Fuchsloch im Krockstein. 35 records from Inventaire chiroptères ferme éolienne de Gurunhuel. 49 records from SILENE-FAUNE-PACA - SYMBIOSE_2017_12_18. 4084 records from Subtidal macrobenthos monitoring in function of a foreshore suppletion at the Belgian coast, period 2013-2016. 27 records from Occurrence of mammalia relicts at site Vindija. 70 records from Plan de gestion 2015 - 2019 du site du Coteau de Monco (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 14 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de LESSIEUR David. 23216 records from Species inventories NP Öewersauer, Recorder-Lux Database. 192 records from "Schwarzwassertal" bei Pobershau. 78 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Amphibiens - Inventaire non standardisé - FRAPNA74 - 24HNAT. 20163 records from Alterra (NL) - Entomofauna inventory in riverside grasslands. 950 records from Total foraminifera counts of multinet M21/2_MSN647. 1001 records from Museums Victoria provider for OZCAM. 367 records from Duke University Herbarium Algae Collection. 696 records from Herbivorie_Pflanzenebene_2008. 703 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Bocage et boisement. 50787 records from SysTax - Zoological Collections. 253 records from Données naturalistes d'Olivier LAURENT. 12 records from Kindergarten. 5636 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de RAYNARD Philippe. 37536 records from CSIC-Real Jardín Botánico-Colección de Hongos (MA-Fungi). 72 records from Animation du Document d’objectifs du site Natura 2000 FR7200799 - Carrières de Castelculier (47) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 29482 records from Mosses and Liverworts: Records for Kent.. 45 records from Natterjack Toads of Ireland. 1253 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 152 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 135 (N.S) n° 28 (4), 2000 - Données faune. 7 records from Animation du Document d’objectifs du site Natura 2000 FR7200669 - Vallon de la Sandonie (24) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 6 records from Wuhle - Brücke / B1. 1186 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 1815 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes opportunistes de Sylvain BONIFAIT. 196 records from SILENE-FAUNE-PACA - Parc_Naturel_Régional_des_Préalpes_d'Azur_2017_12_18. 7 records from BLM CETAP OPP Sightings. 62 records from Amtsrain Apolda-Zottelstedt. 128 records from Atlas communaux de la Biodiversité du Parc Naturel Régional des Landes de Gascogne (PNRLG) - Inventaire des reptiles 2014. 443 records from MoJ BioBlitz August 2018. 590 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2005 - 2009 Coordonnées GPS Lambert 93. 6 records from Réhabilitation de buses permettant le rétablissement de la continuité écologique du cours d’eau le Habarnet sous l’A64 - Données de la pêche de sauvetage. 82 records from Plan de gestion 2019 - 2023 de la station botanique du Normandin (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1168 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 11 records from Plan de gestion 2013 - 2017 du site de la Butte de la Lot (33) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 9 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Annie JUGLAS. 4 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Joël BRIED. 13 records from Meiofauna abundance in sediment core 54301-009. 316 records from UF FLMNH Ichthyology. 105 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 20495 records from Inventaire de la flore de Charente-Maritime 2012-2020 - Inventaire de la flore de Charente-Maritime 2017. 744 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive draine 2007 - 2011 Coordonnées GPS Lambert 93. 684 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE2. 2348 records from Conchological Society of Great Britain & Ireland: non-marine molluscs (Channel Islands). 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 99 records from Dorfrand Mauderode. 17 records from Étude des peuplements d'araignées de Nouvelle-Aquitaine menée en 2020 par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 61 records from Shrews of Poland. 4319 records from NDFF Wall Plants Monitoring Program. 2 records from Archaeal 16S Ribosomal RNA RefSeq Targeted Loci Project. 1 records from Deep sea Syllidae (Annelida, Phyllodocida) from Southwestern Atlantic. 12 records from (Table 1) Analyses of coarse fraction of DSDP Hole 94-609. 9 records from Description of a new genus and species of Chrysopetalidae (Annelida: Polychaeta) from the NE Atlantic, with some further records of related species. 19 records from Meiofauna abundance in sediment core 12930-075. 368 records from Atlas de la Biodiversité Communales sur la Communauté de Commune de Montesquieu - Données faune opportuniste récoltées en marge du protocole IPA. 1870 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 209 records from New data on the dragonfly fauna of the Moulouya River Basin and the Oriental Region, Morocco (Odonata). 31 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 812 records from Marine benthic dataset (version 1) commissioned by UKOOA. 8 records from Animation du plan de gestion conservatoire du marais des Agacats - Suivis amphibiens. 2609 records from European Moth Nights. 11587 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Tony RINAUD. 172 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 23 records from Coleção de Crustacea do Museu Nacional (MNRJ - CARCINO). 1857 records from Inventaire national des Crustacés Décapodes de France métropolitaine - Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 6779 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Macedomeris, a new monotypic doderiinine genus (Diplopoda, Glomerida) from a cave in North Macedonia, Balkan Peninsula. 793 records from Moineau du Poitou - Inventaire de données en Deux-Sèvres. 42 records from Abundance of three benthic foraminifera species in surface sediments of a North-eastern Atlantic Abyssal Locality. 4605 records from Planktic foraminifera abundance in per cent of Hole PRAD1-2. 21 records from Hyolithen - SMF. 65277 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur François FOURNIER. 54012 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 9 records from Convention - Fondation d'Entreprise du Golf de Vidauban pour l'Environnement - Jeu de données convention FEGVE-SPN (numéro 2). 4 records from Sächsische Schweiz (Wehlener Gebiet). 16 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 30 records from ONCFS Réseau Ours brun - Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 2 records from ConDidact Citizen Science Surveys - Spiders 2014. 210 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 928 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Corneille noire 2010 - 2014 Coordonnées GPS Lambert 93. 107 records from vegoek. 6645 records from Hatikka.fi observations. 1 records from Herpetology. 1289 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur JOURDE Rémi. 876 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Geai des chênes 2008 - 2012 Coordonnées GPS Lambert 93. 186219 records from inatura - Erlebnis Naturschau Dornbirn. 35 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 551 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Otter [2010-2014]. 48 records from écotourisme dans le Parc Naturel Régional des Landes de Gascogne (PNRLG) - Données des séjours ornitho. 219 records from Banco de Germoplasma Vegetal del Jardín Botánico de Olarizu (Vitoria-Gasteiz)/Olarizuko Lorategi Botanikoaren Landare Germoplasma Bankua (Vitoria-Gasteiz). 4715 records from Inventaire de la flore de Lot-et-Garonne 2013-2018. 1520 records from Total foraminifera counts of multinet M21/6_MSN784. 448 records from Benthic macrofauna abundance of sediment core 13078-015. 9650 records from Herbario de Universidad de Murcia: MUB. 715 records from Pollen profile from sediment core AV14_K2-1. 242 records from NSW AVH feed. 9 records from Two new species of the previously monospecific genus Guipuzcosoma Vicente & Mauriès, 1980 from Spain, with establishment of Guipuzcosomatidae fam. nov. (Diplopoda: Chordeumatida). 126 records from Etude avifaunistique de la LPO Limousin sur les landes haut-viennoises - Inventaire et suivi Avifaune des landes de la Haute Renaudie. 144 records from Birds ringed with Norwegian rings 1961-1990. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 45 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Ville_de_Fréjus_2017_12_18. 61 records from Ferme éolienne de Saint-Hilaire-du-Maine - Insectes patrimoniaux observés durant les expertises entomologiques en 2014. 23305 records from WTSWW Data: All Taxa (West Wales). 56 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 421246 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 96 records from "Ahrschleife bei Altenahr". 469 records from South Australian Museum Australia provider for OZCAM. 984 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pigeon ramier 2004 - 2008 Coordonnées GPS Lambert 93. 13375 records from Seasearch Marine Surveys in Ireland. 35 records from Urwald 3 (Bad Waldsee). 347 records from MGC Herbarium of University of Malaga (Spain): MGC-Briof dataset. 12 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc). 69 records from Unter hellen Zinnen und finsteren Grotten. 601 records from BCE butterfly data in and around Nothern Italy. 8 records from HBRG Vertebrates (not Badger) Dataset. 7 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6456 records from Base BOMBINA du Parc Naturel régional Lorraine - Modernisation des ZNIEFF du PnrL. 12 records from Occurrence of mammalia relicts at site Niederlehme. 1264 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Grand Voyeux - Suivis scientifiques. 15 records from Collections de coquilles continentales du Muséum d'histoire naturelle de Grenoble. 1 records from Planothidium galaicum sp. nov. (Bacillariophyta, Achnanthidiaceae), a new diatom species from Galician coast, Spain. 190 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes 2019 de Bruno DAUGET. 462 records from (Table 15) Distribution of planktonic foraminifera in the early to early late Oligocene section of ODP Hole 149-900A. 2 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 149 records from Tasmanian Museum and Art Gallery provider for OZCAM. 123 records from Occurrence of mammalia relicts at site Veternica. 6 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Amélie BERTOLINI. 254321 records from Swiss National Mollusca Databank. 589 records from Planktic foraminifera distribution of sediment core SU81-07. 247 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Perdrix rouge 2011 - 2015 Coordonnées GPS Lambert 93. 48798 records from Inventaire de la flore de Dordogne 2015-2019 - Inventaire de la flore de Dordogne 2018. 11 records from Base BOMBINA du Parc Naturel régional Lorraine - ENS inventaires - Parc naturel régional de Lorraine. 5232 records from Natural England bat roost visit records from 2013 onwards. 12 records from Occurrences de Bouquetin ibérique (Capra pyrenaica) collectées par le PNP et le PNRPA. 13008 records from Herbario de la Universitat de les Illes Balears. 42921 records from Naturalis Biodiversity Center (NL) - Aves. 19 records from Inventaire en continu de la ZNIEFF 'Pelouses Calcaires De Saint-Urcisse' - 720020116 - Pelouses calcaires de Saint-Urcisse - Inventaires Oiseaux, Amphibiens & Reptiles opportunistes. 60203 records from National Stag Beetle Surveys (Great Stag Hunts). 1734 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 466 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 47445 records from Marine Offshore Seabed Survey data held by JNCC. 1 records from A review of Labidostomis species similar to L. longimana from southeastern Europe with descriptions of two new species from Greece and Turkey (Coleoptera: Chrysomelidae: Cryptocephalinae: Clytrini). 319 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur LEFEBVRE François. 1475 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 343 records from CSIC-Real Jardín Botánico-Colección de Hepáticas (MA-Hepat). 1230 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 47 records from Occurrence of mammalia relicts at site Sütto_6. 1029 records from Herbarium of Taiwan Forestry Research Institute. 245 records from Fishing with motorized boats in the Belgian littoral area in 1932. 23 records from Ackerrain Plönhagen. 608 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Fourmis SpiPoll 2010-2012. 15022 records from UK Cranefly Recording Scheme - records verified via iRecord. 1004 records from Inventaire Odonates-Rhopalocères 1999-2002 du PNRLG - Données odonates. 17318 records from Swiss National Diplopoda Databank. 4403 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 41575 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Damien AVRIL. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 27 records from Réseau Loup - Lynx ONCFS - Lynx 1995 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 333 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Flore - Inventaire non standardisé - FRAPNA74 - 24HNAT. 68 records from Projet PRD d'Entrepôt Logistique sur les communes d'Illies et de Salomé - Liste de la flore recensée en 2016. 882 records from 1915-2016 Department for Environment Food & Rural Affairs (Defra), Marine Strategy Framework Directive (MSFD) Collation of invasive non-indigenous species. 2 records from Naturalis Biodiversity Center (NL) - Echinodermata. 1150 records from Benthos counted on dredged samples during Valdivia cruise VA53. 16398 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1140 records from Total foraminifera counts of multinet M21/1_MSN608. 159 records from EDP Foz Tua Otter (Lutra lutra) [transects] - Ecological Monitoring Program (2011-17). 1 records from Limonium poimenum (Plumbaginaceae), a new chasmophyte species from Sicily. 2 records from Two new species of cheilostomate Bryozoa from Iberian waters. 11722 records from Universitat de València, Colecciones de Criptógamas: VAL_Lich. 104 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Severine GUYOT. 97 records from Projet de parc éolien de la Croix Guingal, sur la commune de Derval (44 590) - Flore 2017 - Croix Guingal - raccordement externe. 341 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Annales du Musée d'Histoire Naturelle de Marseille (Zoologie). 42 records from Données espèces - Expertise IPE 28. 953 records from Pollen profile Märchenwald B, Harz, Germany. 161 records from Thistles species and abundance. 1 records from Herbier National du Gabon. 18 records from Classic localities of endemic amphibians, reptiles and mammals from the Western Balkans. 360 records from (Appendix 4) Stable oxygen isotope record of Globigerina bulloides and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2040. 10 records from Plan de gestion du Site des Sources - Inventaire Faune. 38 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 5072 records from NRA River corridor survey data from 1990s - River Colne and Tributaries. 720 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Faisan commun 2008 - 2012 Coordonnées GPS Lambert 93. 144 records from PROJET DE CENTRALE PHOTOVOLTAÏQUE A MAUGES SUR LOIRE - données faune flore, centrale photovoltaïque de Mauges sur Loire (49). 34 records from The Italian species of the Chthonius ischnocheles group (Arachnida, Pseudoscorpiones, Chthoniidae), with reference to neighbouring countries. 55 records from Pseudoscorpions of Ireland. 271 records from Norfish: French herring fishery, 1520-1790. 716 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 3089 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Mares. 20375 records from SILENE-FAUNE-PACA - Société_Française_d'Odonatologie_2017_12_18. 1216 records from Total foraminifera counts of multinet M21/6_MSN776. 814 records from flower availability 2008 Hainich. 20 records from Type locality records of Polycystididae species in the world. 173403 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 5 records from Projet de parc éolien de la Croix Guingal, sur la commune de Derval (44 590) - Croix Guingal - Chiro - Transit automnal 2015. 1122 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Stéphane ORIO. 10 records from Collection Echinodermata - ZMB. 60 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi botanique et entomologique pour la gestion de la portée de RTE sur l'emprise de la RNN de Bassée. 3914 records from EDP Foz-Tua: Macrophytes – Ecological Monitoring Program [2011-2015]. 10 records from A revision of Medon. XI. Five new species, additional records, and the first confirmed records from the Oriental region (Coleoptera: Staphylinidae: Paederinae). 626 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 434 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Cliff-nesting birds, prioritary conservation species: fixed observation points [2010-2014]. 1 records from The InBIO Barcoding Initiative Database: Taxonomic notes on Portuguese Microlepidoptera II. Cochylimorpha punctiferana (Ragonot, 1881). 36563 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du Parc Naturel Régional de la Haute Vallée de Chevreuse provenant de la base de donnée du SINP Île-de-France CETTIA. 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 212 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 25 records from Projet d’élargissement à 2x3 voies de l’autoroute A4 sur le Contournement Nord-Est de Metz (CNEM) - Zones de présence d'espèces animales et végétales. 5150 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de ABGRALL Jean-François, Département Santé des Forêts, Ministère de l'agriculture. 12 records from On the taxonomic status of Holothuria (Holothuria) tubulosa (s. s.) from the Algerian coast with the description of a new Mediterranean species, Holothuria (Holothuria) algeriensis n. sp. (Echinodermata: Holothuroidea: Holothuriidae). 23 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi de la reproduction des Lamproies de Planer sur les sites Natura 2000 en Seine-et-Marne. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 2177 records from Jardín Botánico Atlántico, Gijón/Xixón: Herbarium JBAG. 539 records from Système d'Information sur la Nature et les Paysages d'Ile de France - étude entomologique de la ZSC du Bois de Vaires. 7157 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Marcel CRUVEILLIER. 8 records from Herbarium specimens of CBNA (GAP). 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-084. 366 records from Weinberg Reichersdorf. 3975 records from Regroupement d'études et d'inventaires - Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 349 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 22 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" des saligues, (BORDÈRES-CAZÈRES-RENUNG). 3 records from A new solitary, interstitial species of Loxosomatidae (Entoprocta) from the coast of Galicia (NW Spain), Loxosoma discoides n. sp.. 235 records from Plan de gestion 2014 - 2018 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 133 records from (Table 1) Distribution of planktonic foraminifera species in Core ML2_66. 8 records from Occurrence of mammalia relicts at site Kogelstein. 11 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de Lépidoptères de Bruno DAUGET - Dépt du LOIR-ET-CHER (41). 735 records from Pollen analysis of sediment profile NI0 from Niklassee. 2097 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 316 records from CONN. 7294 records from NHMO Bird collection. 96 records from Kherson State University herbarium (KHER), Department of Botany. 96739 records from LifeWatch observatory data: permanent Cetacean passive acoustic sensor network in the Belgian part of the North Sea. 6594 records from Nijmegen Natural History Museum (NL) - Herbarium. 754 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2007 - 2011 Coordonnées GPS Lambert 93. 950 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 2519563 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 2 records from Nothocasis rosariae sp. n., a new sylvicolous, montane species from southern Europe (Lepidoptera: Geometridae, Larentiinae). 2334 records from Données du programme 50000 observations pour la forêt. 6845 records from Protocole de recensement des collisions entre la faune sauvage et les véhicules de la Direction interdépartementale des routes Centre-Est - Données de mortalité de la faune par collision avec les véhicules sur le réseau routier de la DIR Centre-Est. 960 records from SILENE-FAUNE-PACA - Département_du_Var_2017_12_18. 7 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 45 records from Plan de gestion 2007 - 2011 du site du Coteau de Peyroutet (47) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 31 records from Projekt Wahner Heide. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Laurence CAUD. 35 records from Projet de parc solaire Figanieres - Oiseaux - inventaire non protocolé. 94 records from Inventaire en continu de la ZNIEFF 'Forêt du Verdus' - 720012953 - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 630 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 212 records from Mollusques continentaux de France - Inventaire malacologique du site Natura 2000 FR9301547 du Grand Coyer (2007, ONF/MNHN). 2 records from Collection Arachnida - ZSRO. 1 records from Plan de gestion 2018 - 2022 du site de la Butte de la Lot (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 3230 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 3 records from Exotic specimens butterflies at Museum Zoologi Bogor, Indonesia. 2 records from In situ observations of Stygiomedusa gigantea. 144 records from Inventaire biodiversité du site Pierre Fabre de Saint-Sulpice. 128 records from Intermountain Herbarium (fungi, not lichens), Utah State University. 288 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Observation d'amphibiens et d'odonates réalisées par le CEN Aquitaine dans le cadre du suivi des mares de substitution et de compensation. 1332 records from Inventaire Entomologique, E. DECAUX 1998 - Inventaire des données récoltées par Emmanuelle DECAUX et la SEL. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 4 records from Inventaire en continu de la ZNIEFF 'Terrain militaire de la Croix-blanche' - 720020097 - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Mathieu TAILLADE. 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 2 records from Plan de gestion 2013 - 2018 du Lac de La Prade (33) mené par le CEN Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 12 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Occasionnelle du Loup en 1997. 1074 records from Distribution and community structure of benthic copepods in the Delta area and the Ems-Dollard between 1976 and 1981. 155 records from CAS Entomology (ENT). 226485 records from Programme CarNET B (Cartographie Nationale des Enjeux Territorialisés de Biodiversité Remarquable) - Carnet B Lorraine. 215 records from Naturalis Biodiversity Center (NL) - Pisces. 42 records from Inventaire en continu de la ZNIEFF 'Lettes de Baine de Lédasse' - 720030126 - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 320 records from Marine algal (seaweed) flora of Formigas Islets, Azores. 1976 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 1117 records from Historical landings from the Rijeka (Croatia) fish market between 1914 and 1932. 61816 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 72 records from Atlas de la Biodiversité Communales sur la Communauté de Commune de Montesquieu - Observations d'orthoptères (inventaire) réalisées par Locusta. 261 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données Coléoptères OGE transmises par Benoît Toury. 278074 records from Seasearch Marine Surveys in England. 121 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste PRATTE Olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 697 records from HSS-carpoteca (HSS-C) Finca La Orden-Valdesequera (CICYTEX). Junta de Extremadura. 2389 records from PAMP-tracheo: Vascular plants in Pamplona Basin (Navarra, Spain). Undergraduate thesis, D. Vicente. 27033 records from Fishes in MZNA-VERT: cyprinid and salmonid communities in the rivers Erro and Urederra (Spain). PhD project, Cristina García-Fresca. 12 records from Développement du pôle commercial de Peyssilieu (Meyzieu 69) - Inventaire lépidoptère_Meyzieu - Pôle commercial de Peyssilieu. 875 records from Mammal records captured from Licence Returns submitted to Natural Resources Wales. 57 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 2848 records from Collection Trichoptera - SMF. 1169 records from SEWBReC Slime Molds (South East Wales). 3573 records from VIT - Lepidotheca (The Natural History Museum of Álava). 7 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" de la tourbière de Pont-Neuf (SAINT-MICHEL-ESCALUS). 5279 records from Mutualisation des données naturalistes pour le rapportage Natura2000 en 2017 - Synthèse 10x10km des espèces de la Directive Oiseaux recensée par le Groupe Ornithologique des Deux-Sèvres de 2013 à 2017. 93 records from Projet éolien - Insectes - Inventaire non protocolé. 184 records from Occurrence of mammalia relicts at site Raj Cave. 774 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette des champs 1997 - 2001 Coordonnées GPS Lambert 93. 41 records from Arizona State University Hasbrouck Insect Collection. 86 records from Vascular plant herbarium TRH, NTNU University Museum. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 137 records from Plan régional d'actions en faveur des odonates (PRAO) : 3ème phase (2017 - 2018) menée par le CEN Aquitaine - Observations faunistiques fortuites réalisées lors de journées de prospections animées par le CEN Aquitaine. 930 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle turque 2008 - 2012 Coordonnées GPS Lambert 93. 3537 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Alain BERLY. 22017 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 34 records from Réseau Loup - Lynx ONCFS - Lynx 1994 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 371 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 47 records from A worldwide catalog of the Vermileonidae (Diptera: Brachycera). 639 records from Inventaires naturalistes du Service du Patrimoine naturel / UMS PatriNat - Inventaire de l'îlot du Lédénez Vraz. 373 records from Evaluation des MAEC - Inventaire Oiseaux sur les prairies en MAEC. 31034 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de D'ONOFRIO Patrice. 266 records from Berlin-Brandenburg Plant Collection 2006. 1455 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 151 records from CEDaR Online Recording. 814 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle des bois 1997 - 2001 Coordonnées GPS Lambert 93. 517 records from DSMZ Prokarya Collection Catalogue. 86 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 537 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Delphine MONTAGNE. 2814 records from Atlas des papillons de jour et des libellules du Languedoc-Roussillon - Données CEN L-R papillons/libellule. 207 records from Revision of the spider genus Stygopholcus (Araneae, Pholcidae), endemic to the Balkan Peninsula. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 5268 records from Global Lacustrine Diatoms. 7981 records from Larvae of decapods off Portuguese coast from 1986 to 1994. 368 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Julien PIOLAIN. 202 records from The InBIO Barcoding Initiative Database: Diptera 01. 1238 records from Insect Collection (CeStuBio). 92 records from Nottekanal, Klasse 7 - 10. 912 records from Total foraminifera counts of multinet M21/2_MSN657. 74 records from SILENE-FAUNE-PACA - Syndicat_Mixte_de_Défense_des_Berges_de_l'Asse_2017_12_18. 235 records from Parc éolien du Mont de Bagny II - Inventaire de la flore sur l'aire d'étude. 11 records from Historical findings of Salvinia natans in Ukraine. 4704 records from Inventaire des Mollusques Sphaeriidae de France. 17073 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de CORNIC Jean-François. 744 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette des champs 2000 - 2004 Coordonnées GPS Lambert 93. 86 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 74 records from Données espèces - Expertise IPE 69. 29 records from Diagnostic des parcelles de zones humides "voie verte" sur la commune de St-Front-de-Pradoux (24) mené en 2017 par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 2652 records from Seed bank grassland. 576 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 4 records from A taxonomic revision of the Palaearctic members of the Formica rufa group (Hymenoptera: Formicidae) - the famous mound-building red wood ants. 6621 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 39 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Insectes - Inventaire non standardisé. 50 records from Flora und Fauna im Brexbachtal. 81251 records from MICROBIS database. 259 records from Estonian Ornithological Society (BirdLife Estonia). 92 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 615 records from Fauna marina de la costa vasca - Sistema de Información de la Naturaleza de Euskadi. 123 records from Birdrace-Professorenteam-Münster. 2488 records from RSPB Reserves breeding bird surveys. 627 records from Bryopyhtes in forest indices and traits. 1 records from Regroupement d'études et inventaires - Suivis botaniques. 485667 records from Swiss National Grasshoppers Databank. 144 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaires complémentaires du Fort d'Aubervilliers (93). 79 records from Grand Rhinolophe et trame verte bocagère en Poitou-Charentes - Données sur les colonies de reproduction et d'hivernages des chiroptères de Charente-Maritime. 84531 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 210 records from Pollen profile II/B at Krumbach, Germany. 18 records from Meiofauna abundance in sediment core 12930-029. 63 records from Hochschule Zittau/Görlitz. 13065 records from Weevil and Bark Beetle records via iRecord. 145 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Bergemer Jean-Denis provenant de la base de donnée du SINP Île-de-France CETTIA. 243 records from Projet éolien de Camblain-Châtelain (SEPE Le Mont Duquenne) - FLORE. 192 records from Loup 2009 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 410 records from Woodland Survey. 3324 records from Collection botanique Le Grand A. (BOUM). 310 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 8 records from HBRG Other Invertebrates Dataset. 5 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 111 records from University of Algarve and ICNB Cetacean Sightings 1999. 18139 records from Expertises des CEN d'Occitanie en partenariat avec les laboratoires de recherche et universités - Données CEN L-R SEMCLIMED. 37 records from Réseau Loup - Lynx ONCFS - Lynx 2009 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 690 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Annales de la Société entomologique de France [1832- ]. 16226 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 195 records from Royal Belgian Institute of Natural Sciences Echinodermata collection. 16 records from Plan de gestion 2019 - 2023 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 7 records from Plan de gestion 2012 - 2016 du site des tourbières de Mées (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 4760 records from SEWBReC Algae and allied species (South East Wales). 72176 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 3 records from Distribution of Quinqueloculina sp. in sediment core 13200-078. 165 records from Programme les sentinelles du climat - effets du changement climatique sur la biodiversité en région Nouvelle-Aquitaine - Observations d'odonates réalisées par la Réserve d'Arjuzanx selon le protocole STELI adapté pour le programme. 99 records from Programme LIFE CROAA - Eradication de la Grenouille taureau : Tir des individus. 232 records from Elaboration du DOCOB du site Natura 2000 ‘Haute Cize’ (FR7212015) - Inventaire avifaune. 4095523 records from iNaturalist Research-grade Observations. 8928 records from City of Amsterdam (NL) - Fyke Fishing Piet Ruiter. 93 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de ERARD Marc. 5 records from The Anagyrus (Hymenoptera: Encyrtidae) parasitoids of the obscure mealybug Pseudococcus viburni (Hemiptera: Pseudococcidae) in Spain, with description of a new species. 48 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Ouest. 2262 records from (Table 5) Stratigraphic distribution of calcareous nannofossil taxa in ODP Hole 149-898A. 492 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 35 records from Bohemannia auriciliella (Nepticulidae) specimen data. 36 records from Réseau Loup - Lynx ONCFS - Lynx 1996 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 97 records from Projet de création d'une usine de fabrication de granulés de bois sur la commune d'Anor (59) - Expertise faune flore- TAUW FRANCE - avril 2017. 677 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - données aranéologiques de ROLLARD Christine. 3171 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1245 records from Gipuzkoako Foru Aldundiaren Landareen Germoplama Bankua / Banco de Germoplasma Vegetal de la Diputación Foral de Gipuzkoa. 217 records from Atlas communaux de la Biodiversité du Parc Naturel Régional des Landes de Gascogne (PNRLG) - Inventaire des odonates 2014. 222 records from Plan Local d'Urbanisme (PLU) de La Brède - Inventaire faune. 1 records from Happywhale - Blue Whale in North Atlantic Ocean. 759 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette des champs 2004 - 2008 Coordonnées GPS Lambert 93. 1079 records from Mediterranean seabird surveys 99/00/02. 695 records from Amphibia collection of the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 694 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de CARR David. 94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 283 records from Eurytemora affinis in the Sluice Dock Oostende (1970-1971). 64 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 1030 records from Polish seed gene bank – historical passport data of accessions. 63 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Julien Schwartz. 3 records from The AAU Herbarium Database. 1 records from Graureiher in Lans. 949 records from Badger and Habitats Survey of Ireland. 21 records from New and remarkable leafhoppers and planthoppers (Hemiptera: Auchenorrhyncha) from Switzerland. 5 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Sophie HALM. 1376 records from Bird Monitoring 2017, Meise Botanic Garden. 970 records from Historical landings for the lagoon of Venice (Italy) between 1945 and 2001. 1711 records from Hypogean macro-Crustacea records. 318 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 773 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle des bois 2012 - 2016 Coordonnées GPS Lambert 93. 182 records from Heritage Trees of Ireland. 81 records from Etat initial de la faune pour la construction de la liaison RD656/RD119 et des carrefours associés (Amorce de la rocade Ouest d'Agen) - Inventaire et suivi Faune. 95 records from Elaboration des DOCOB des sites Natura 2000 ‘Plateau d’Argentine’ (FR7200810) en 2009 et ‘Réseau hydrographique de la haute-Dronne’ (FR7200809) en 2010 - Inventaire et suivi Entomologique de Desmond KIME. 10 records from Plan de gestion 2020 - 2024 du site du Coteau de Casserouge (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 1 records from OBI - Robert F. Hoover Herbarium, Cal Poly State University. 30 records from Collection Polychaeta - ZSRO. 1140 records from Plasm bearing foraminifera counts of multinet POS200/6_MSN837. 140 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 41167 records from Herbario de la Facultad de Ciencias Biológicas de la Universidad Complutense de Madrid (MACB). 764 records from Centre d'Estudis Avançats de Blanes. Limnological Observatory of the Pyrenees - Fitoplancton de lagos pirenaicos. 157 records from Tetranychus urticae literature occurrences in a predator-prey system: Phytoseiulus persimilis (Acari: Phytoseiidae) and Tetranychus urticae (Acari: Tetranychidae). 5 records from RISC Non-Native Species Records for Zebra Mussel. 50 records from Leben in den Elbwiesen. 435 records from Données LIFE + DESMAN CEN MP. 80 records from Range table from benthic foraminifers in ODP Hole 149-899B. 5320 records from Zooplankton studies in the Southern Bight of the North Sea between 1971 and 1974. 157 records from Projet éolien de la Briqueterie - Inventaire naturaliste de la Centrale Eolienne La Briqueterie. 45 records from MSB Bird Collection (Arctos). 46 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 147 (N.S) n° 40 (2), 2012 - Données faune. 7583 records from Naturhistorisches Museum Mainz, Zoological Collection. 1 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 100 records from Données d'observation d'écrevisses exotiques envahissantes en Haut de France et Normandie sur la période 2014 à 2018. 681 records from Projet LEVANA - Inventaire et suivi Rhopalocères et Zygènes en Entre-deux-mers. 190 records from Freshwater fish records via iRecord - additional species. 912 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1194. 2 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Alice DECHRISTé. 539 records from Ichthyology Collection - Royal Ontario Museum. 108 records from Atlas de la Biodiversité Communales sur la Communauté de Commune de Montesquieu - Données faune opportuniste récoltées en marge des protocoles Amphibien & Reptiles. 141 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Angé christofer provenant de la base de donnée du SINP Île-de-France CETTIA. 330 records from Benthic macrofauna abundance of sediment core 13200-017. 2 records from Euscorpius thracicus sp n (Scorpiones: Euscorpiidae) from Bulgaria. 182287 records from Muskrat trapping data in the Netherlands 1987 – 2014. 2 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 44 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 2131 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 455 records from Données naturalistes acquises sur les sites du MNHN. 3 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Atlas de la flore de la forêt du Madrillet. 71 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Amphibiens - Inventaire non standardisé. 3666 records from RAVON (NL) - Network Ecological Monitoring Reptiles. 13237 records from European Invertebrate Survey (EIS-NL) - Orthoptera Specimen. 798 records from Plateforme AUVERGNE-DREAL Auvergne - DREAL Auvergne - Mammifères - 2015. 9060 records from Atlas des oiseaux nicheurs de France réalisés par carte IGN50 - Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification possible. 103 records from Evaluation of the effect of disposal of dredging material on macrobenthos communities in the Maas plain (1988). 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 93 records from Invertebrate collection. 1 records from Plan de gestion 2016 - 2020 du site du Coteau de Savoye (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 20 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Jérôme ALLOU. 39 records from Inventaire en continu de la ZNIEFF 'Pechs De Bouyssou Et De Vitrac' - 720020098 - Pechs de Bouyssou et de Vitrac - Inventaires Oiseaux IPA. 75 records from Species diversity of Myrmecofauna (Hymenoptera, Formicidae) on the southern slope of Djurdjura National Park (Northern Algeria). 581 records from PIROP Northwest Atlantic 1965-1992. 2 records from Distribution of Quinqueloculina sp. in sediment core 13200-081. 91 records from Mutualisation des données naturalistes pour le rapportage Natura2000 en 2017 - Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée de 2013 à 2017. 125 records from Plan de gestion 2013 - 2018 du Lac de La Prade (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 474 records from Projet d'ouverture d'une gravière sur la commune de St-Michel de Rieufret, lieudits - Données brutes biodiversité - St Michel de Rieufret. 2 records from UWFC Ichthyology Collection. 84 records from Etude d'aménagement foncier lié à la desserte du CHNDS - Inventaire de Lépidoptères et des Odonates. 816 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle des bois 1996 - 2000 Coordonnées GPS Lambert 93. 62137 records from Non-target effects of Metarhizium brunneum on soil microbial communities. 167 records from Auburn University Museum of Natural History Invertebrates. 123 records from BIRDRACE Unterste Niederrhein-Rennvögel. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 3575 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 74 records from Animation du site Natura 2000 ‘La Vallée de l'Avance’ (FR7200739) - Données opportunistes. 44 records from Construction d'un projet photovoltaïque flottant - Données CALIDRIS. 50 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes opportunistes de Cedric DEVILLEGER. 27 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 2 records from Marie-Victorin Herbarium (MT) - Bryophytes. 7 records from Benthic macrofauna abundance of sediment core 12930-068. 113 records from iHerbarium. 2 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 339 records from Regroupement d'études et d'inventaires - Inventaire Chiroptères collectées par contact en main. 15 records from Plan de gestion 2016 - 2020 du site du domaine de Rodié (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 273 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Clémentine Gand. 1 records from Isoperla vjosae sp. n., a new species of the Isoperla tripartita group from Albania (Plecoptera: Perlodidae). 48 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Franck UTEAU. 63 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 57 records from Mauervegetation,Flechten und anderes. 12315 records from BCE butterfly data expert holiday data throughout Europe. 175 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 85 records from Parc éolien de la Société d’Exploitation du Parc Eolien des Noues à Blacy (51) - Inventaire non protocolé de la flore. 109 records from BIRDRACE Die Borner. 272 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 401 records from Noble Chafer: Post-BAP records from 1998 onwards. 1041 records from Données de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS 2015 Chiroptères, Maculinea, Cistude d'Europe. 29 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Denis VINCENT. 2576 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Anaïs MAS. 689 records from RISC Non-Native Species Records for Muntjac. 3 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 65 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 25 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 41 records from Base BOMBINA du Parc Naturel régional Lorraine - Natura 2000 Complexe de l'étang de Lindre, forêt de Romersberg et zones voisines. 257529 records from Wikiplantbase #Toscana. 42 records from Seguimiento del castor en el País Vasco - Sistema de Información de la Naturaleza de Euskadi. 18 records from SILENE-FAUNE-PACA - ALTERECO_2017_12_18. 42 records from Schulgarten Paul-Schneider-Schule, Münster. 17 records from Mammal collection NTNU University Museum. 928 records from Biofokus. 7370 records from Anymals+plants - Citizen Science Data. 20 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 2078 records from DASSH Data Archive Centre volunteer sightings records. 174 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2008. 373440 records from Sierra Nevada Atmospheric-Pollen Data set (SNOWPOLL). 991 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste CARON Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 41 records from Happywhale - Humpback Whale in North Atlantic Ocean. 105427 records from ABV - Common breeding birds in Flanders, Belgium (post 2016). 2908 records from TTU Mammals Collection. 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 3 records from Synonymy of the ant-loving cricket Myrmecophilus termitophilus Ma an, 1959 (Orthoptera: Myrmecophilidae). 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 684 records from Total foraminifera counts of multinet M26/1_MSN845. 1549 records from Oil Beetle Recording Scheme - records verified via iRecord. 12 records from Rehabilitated loggerhead from southern Italy - 2 (aggregated per 1-degree cell). 2130 records from EDP Foz-Tua: Phytobenthos – Ecological Monitoring Program [2011-2015]. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 273 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 3093 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 820 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle turque 1997 - 2001 Coordonnées GPS Lambert 93. 4729 records from Suivi des oiseaux de passage : programme FLASH - Programme FLASH : Répartition Grive mauvis 2012 - 2016 Coordonnées GPS Lambert 93. 211 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette lulu 2000 - 2004 Coordonnées GPS Lambert 93. 29 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Etienne ROGEAU. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Myriam LABADESSE. 3 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Eric PIQUET. 735 records from EDP Foz-Tua: Vascular Flora – Complementary Studies and Baseline Year of the Ecological Monitoring Program [2011]. 831 records from Inventaires de la faune exotique envahissante - Inventaire sur les vers plats terrestres introduits en France métropolitaine et en outre-mer. 307 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 56 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 65 records from Réseau Loup - Lynx ONCFS - Lynx 2015 présence Occasionnelle Mailles_10km_LAEA Réseau Loup-Lynx ONCFS. 44 records from CUMV Fish Collection. 50283 records from EURISCO, The European Genetic Resources Search Catalogue. 165 records from MUST, Insecta. 24 records from Suivi et déplacement d'amphibiens pour la construction de la liaison RD656/RD119 et des carrefours associés (Amorce de la rocade Ouest d'Agen) - Déplacement d'amphibiens dans le cadre du chantier. 9 records from Plan de gestion 2008 - 2012 du site de la Butte de la Lot (33) mené par le CEN Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 1213839 records from Données ONF faune-flore-fonge. 13 records from Observations occasionnelles de taxons par les agents de la Fédération (hors inventaires scientifiques) - Inventaire opportunistes Faune. 6448 records from The New York Botanical Garden Herbarium (NY). 100 records from BIRDRACE Stuttgart 100 trööt. 48 records from Deutsche Schule Budapest. 1463 records from Regroupement d'études et d'inventaires - Regroupement de données rhopalocères récoltées sur la période de 2010-2015 par Cistude Nature. 16 records from Occurrence of mammalia relicts at site Trebacki krs. 42 records from Notice de gestion 2019 - 2023 de la bande de servitude de l'artère Girland (40) de Teréga mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 104471 records from Institut Botanic de Barcelona (IBB, CSIC-Ajuntament de Barcelona), BC-Plantae. 1394 records from Ferme éolienne de Mauprévoir - Données Mauprévoir - oiseaux. 1140 records from Total foraminifera counts of multinet M12/3_MSN561. 6797 records from Collection Arachnology SMF. 2176 records from University of Tennessee Fungal Herbarium. 2170 records from University of Michigan Museum of Zoology, Division of Mollusks. 192 records from Suivi de l'évolution des populations - Inventaire et suivi Rhopalocères – Protocole STERF. 309 records from Nannofossil abundance of Hole 94-609B. 5 records from Occurrence of mammalia relicts at site Siebenlinden 3. 43731 records from Données acquises par le Conservatoire botanique national du Bassin parisien et son réseau (bénévoles, associations, autres structures professionnelles) - Données acquises via le réseau du Conservatoire botanique national du Bassin parisien. 1436 records from Inventaires et suivis sites compensation contournement sur la commune de DAX - Données opportunistes. 258286 records from Bird tracking - GPS tracking of Western Marsh Harriers breeding near the Belgium-Netherlands border. 1 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 1223 records from DASSH Data Archive Centre Academic Surveys. 11 records from A new species of Streblospio (Polychaeta: Spionidae) from the northern Adriatic Sea (Mediterranean Sea). 378 records from Freshwater Diversity Identification for Europe (FREDIE) - funded by the German Leibniz association ( SAW-2011-ZFMK-3). 222 records from Occurrence of mammalia relicts at site Roc de Combe. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 245 records from Suivi de travaux : Vannes de l’Estrabeau (Engranne) Moulin des 4 ponts (Gestas) - Inventaire macroinvertébrés. 148 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 176 records from Données odonates extraites de la base de données du CEN Midi-Pyrénées. 397165 records from Natural England Marine Monitoring surveys. 27 records from Inventaires sur le réseau Aquitaine Nature du PNR Périgord-Limousin - Inventaires sur la lande de Moussigou par le CEN Aquitaine. 33 records from (Appendix 2) Abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core SU81-18. 15123 records from Ground Beetle Recording Scheme - data verified via iRecord. 2 records from Collection Tunicata SMF. 58 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Pascal TARTARY. 136 records from Taxonomic, distributional and biological study of the genus Agrilus (Coleoptera Buprestidae). Part III. 3100 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 22 records from Parc éolien d'Argillières - ornithologie hivernage. 10 records from Kita-Wäldchen Fuchsturmweg Jena. 292 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 959 records from Coleoptera Collection. 7 records from Animation du site Natura 2000 ‘Réseau hydrographique des affluents de la Midouze’ (FR7200722) - Inventaire et suivi Ecrevisses. 416 records from Loup 2016 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 23 records from ONCFS Réseau Ours brun - Ours 2016 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 688 records from Classic localities of terrestrial Mollusca from the Western Balkans. 493 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Sylvain VRIGNAUD. 14444 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 61 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Willy CHENEAU. 94 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Lefevre Benjamin provenant de la base de donnée du SINP Île-de-France CETTIA. 213 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Naturalia_2017_12_18. 102 records from Waldwandel in Monschau-Mützenich-Boverei. 39 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Chevêche d'Athena. 2 records from Allopatric cryptic diversity in the alpine species complex Phtheochroa frigidana s. lat. (Lepidoptera: Tortricidae). 21 records from Enquête sur 3 mammifères protégés : le Muscardin, le Campagnol amphibie et la Crossope aquatique - Données mammifères Phase 1 récoltées par Vienne Nature. 302654 records from Welsh Invertebrate Database (WID). 6050 records from Vertical distribution of the free-living Plathelminthes (Turbellaria) from the sandy beaches of the Belgian coast in 1985 and 1986. 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 1 records from Plan de gestion 2015 - 2020 du site du Coteau des Chaupres (24) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 256 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur PRESSE Tony. 4879 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Bulletin mensuel de la société linnéenne de Lyon [1932- ]. 1469 records from Opération d'aménagement Vallée Créative - Bordeaux Métropole - Inventaire Faune. 201076 records from Freshwater fish of the Netherlands, 1800-2019. 3330 records from Dipterists Forum - Recording Scheme - Stilt & Stalk Flies. 40648 records from Abundances and biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Scorff river (France). 45 records from Projet de parc éolien de la Croix Guingal, sur la commune de Derval (44 590) - Croix Guingal - avifaune nidification 2014. 20846 records from Regroupement d'études et inventaires de la Réserve Naturelle de l'Etang des Landes - FR3600158 - Ensemble des données. 9504 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 2220 records from Évaluation et préservation de la biodiversité dans les anciennes carrières de Charente-Maritime - Inventaire Faune. 714 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette des champs 2009 - 2013 Coordonnées GPS Lambert 93. 192 records from Benthic foraminiferal assemblage (dead) in MUC OB10-K, size fraction >150 µm. 23792 records from Long-Term Monitoring Network Vegetation Quadrats. 608 records from Observations naturalistes hors étude réalisées par les organismes utilisant la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques hors étude réalisées par Nature en Périgord. 337 records from Bell Museum plants. 1075 records from Inventaire Rhopalocère 2008 du PNRLG - Inventaire et suivi Rhopalocères. 142 records from Parc Eolien Les 7 Domaines - Inventaire des oiseaux migrateurs en 2013 et 2014. 119 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 3 records from Plan de gestion 2015 - 2019 du site du Coteau de Casserouge (47) mené par le CEN Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 20515 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pierre FRAPA. 12 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Vincent LABOUREL. 7 records from Collection Crustacea ZMG. 83 records from Naturpark Kottenforst-Ville 16.6.09. 220544 records from Inventaire permanent de la flore du massif armoricain. 5 records from Inventaire des sangsues du Nord-Ouest de la France - réalisation d'un guide à destination du grand public et des naturalistes - Inventaire des sangsues - détermination des échantillons de l'enquête participative - Subvention UMS Patrinat. 661 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de l'enquête Escargots de l'ONEM (onem-france.org). 63 records from Matter enrichment of the macrofauna community of MAC station 13200-005. 249 records from Study of the biotic environment in the Sluice Dock in relation to oyster farming between 1960 and 1964. 2390 records from Observatoire des sites majeurs - LAGUNES - Inventaire et suivi Leucorrhines sur les lagunes Natura 2000. 118 records from Natur aus zweiter Hand am Muldestausee. 244355 records from BRERC Notable Species records within the last 10 years. 1 records from Plan de gestion 2020 - 2024 du site du Coteau de Casserouge (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Nouvelle-Aquitaine. 25 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Julien ROBAK. 23 records from TBW-Schafberg. 172 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Serge Gadoum. 3 records from Base BOMBINA du Parc Naturel régional Lorraine - Amphibiens filet / Communauté de communes Chardon Lorrain. 919 records from WFVZ Bird Collections. 6388 records from NHMO DNA Bank Vascular plants collection. 3368 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste MUNIER THIERRY provenant de la base de donnée du SINP Île-de-France CETTIA. 4268 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Observations et collection de Coléoptères d'Alain Sadorge. 79 records from Umgebung von Schorndorf. 95351 records from Amplicon sequencing of Tara Oceans DNA samples corresponding to size fractions for protists.. 11 records from Hidden diversity within the Nemastoma bidentatum Roewer, 1914 complex (Opiliones: Nemastomatidae) Part I: Morphological evidence. 19872 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 1. 9613 records from Freshwater fishes of the Western Balkans. 44601 records from Marine data from Natural Resources Wales (NRW) Technical Support (Research & Monitoring) Contracts, Wales. 330 records from kznm-entomology-collection. 43 records from JCT AVH data. 2177 records from University of Tennessee Bryophyte Herbarium. 132 records from Mutualisation des données ZNIEFF en ex-Limousin - Données chiroptères transférées du GMHL à LNE. 10 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 2662 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 16924 records from Censo de ardeidas invernantes y nidificantes de la Comunidad Autónoma del País Vasco. 6541 records from Likona Invertebrates. 80 records from Ferme éolienne d'Arnac sur dourdou - Avifaune. 56 records from Données espèces - Expertise IPE 68. 129368 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 1 records from Suivi des conditions de franchisement des ouvraes de protection à la mer par les civelles et autres espèces en fonction des modes de gestion mis en place. - Inventaire et suivi. 40 records from Distribution of meiobenthos in sediment core M23_199 (2) of the northeastern Atlantic (Table 1). 75 records from Coordination PRA Loutre et suivi du castor en Limousin - Inventaire Mammifères Aquatiques. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 19173 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 103 records from Acoustic detections from research cruises in the Med sea, 1994-2001. 38 records from BB-Biodiversität a. 5 records from Collection Myriapoda - SNSD. 64 records from Animation technique des sites Natura 2000 ‘Barthes de l'Adour’ - Suivis rapaces 2013 - Site Natura 2000 des Barthes de l'Adour. 203 records from Parc éolien des Landes de Jugevent - Flore. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 78612 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1 records from Notes on the subspecies of Plagionotus arcuatus (Linnaeus, 1758) with description of a new subspecies from Iran (Coleoptera: Cerambycidae). 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 3546 records from Dorset SW Pilot species dataset. 250 records from Etude naturaliste du projet de parc éolien de Londigny Energies. 2560 records from Mesures compensatoires autoroutes - Données mesures compensatoires ASF - ex région M-P. 2 records from Typification of the name Genista micrantha Gómez Ortega (Leguminosae). 2053678 records from FLORIVON. 144 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste zeitouni kevin provenant de la base de donnée du SINP Île-de-France CETTIA. 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 9 records from Benthic macrofauna abundance of sediment core 13077-087. 154 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Philofauna provenant de la base de donnée du SINP Île-de-France CETTIA. 32 records from SD - SD Herbarium, San Diego Natural History Museum. 194 records from Suivis faunistiques du site du Moulin de la Ville - Suivi Odonate - STELI. 100 records from (Table 5) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the Lesches en Diois section. 1092 records from Royal Belgian Institute of Natural Sciences Reptile collection. 90 records from Regroupement d'études et inventaires - Inventaire et suivi de la faune écrasée. 1144 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 4738285 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 90 records from Données espèces - Expertise IPE 6. 45 records from Flusswerder in der Weser (Hameln). 177 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 36227 records from Observations.be - Orthoptera occurrences in Wallonia, Belgium. 31 records from Animation du Document d’objectifs du site Natura 2000 FR7200666 - Vallées des Beunes (24) menée par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 596 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Stanislas WROZA. 43 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Plan d'aménagement Forêt de Claye-Souilly. 19 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 80 records from Données d'observation d'écrevisses exotiques envahissantes en Provence Alpes Côte d'Azur et Corse sur la période 2014 à 2018. 1028 records from Programmes d'étude et de conservation de populations d'espèces particulières (hors PNA et PRA) - Données CEN M-P espèces. 69921 records from England Non Native Species records 1965 to 2017. 148 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Claire BETBEDER. 1588 records from Non Native Species Across Wales (1989 to 2012). 109 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 12 records from DBL_Life. 1142 records from Abundances and biological traits of the juveniles lamprey sampled in the survey of lamprey abundance Indice on the Scorff river (France). 10 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste LAIGLE Guillaume provenant de la base de donnée du SINP Île-de-France CETTIA. 8532 records from LifeWatch observatory data: zooplankton observations by imaging (ZooScan) in the Belgian Part of the North Sea. 1246 records from Océanopolis mammifères marins en Bretagne 1993-2015. 26395 records from BLS Rare and Threatened Lichen Records: England. 936 records from Animation technique des sites Natura 2000 ‘Barthes de l'Adour’ - Animation des Docobs des barthes de l'Adour. 1140 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 1112 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 6498 records from Eden Arthropod Azores Database. 608 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V29-179. 28 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 9 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Emilien HENRY. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 18 records from Etat initial de la faune pour la construction de la liaison RD656/RD119 et des carrefours associés (Amorce de la rocade Ouest d'Agen) - Données bibliographiques Faune. 69 records from Entdeckertour am Muldestausee 1/05. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 122 records from SILENE-FAUNE-PACA - BIOTOPE_2017_12_18. 40 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Mickaël PELLETIER. 85 records from Réseau Loup - Lynx ONCFS - Lynx 2006 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 108 records from BIRDRACE Diesmal sehen wir mehr. 1338 records from Weevils of Poland. 433 records from Envoi de données complémentaires disponibles à la SFEPM pour l'atlas des Mammifères de France - Données Loutre compilées par la SFEPM pour compléter les cartes de l'atlas national des Mammifères.. 6 records from Parc éolien d'Argillières - chiroptères en altitude. 1 records from Animation du Document d’objectifs du site Natura 2000 FR7200666 - Vallées des Beunes (24) menée par le CEN Aquitaine - Observations faunistiques (suivi par piège photographique) réalisées par le CEN Aquitaine. 315 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 11 records from New and confirmed records of fruit flies (Diptera, Tephritidae) from Italy. 209 records from Plan de gestion des Marais du Conseiller - Inventaire et suivi Faune. 675 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 183 records from Données espèces - Expertise IQE 44. 14261 records from Atlas communaux de la biodiversité du Parc Naturel Régional des Landes de Gascogne 2014-2020 - Inventaire de la flore du PNRLG 2016 (Gironde). 292 records from Campagne d'éradication de la Grenouille taureau (Lithobates catesbeianus) sur le territoire du Parc naturel régional Périgord-Limousin - Campagnes de piégeage et de tirs menées de 2006 à 2014. 11032 records from Compte-cardobs convention Eurovia - Jeu de données convention Eurovia-SPN-2012-2016. 915 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle turque 2004 - 2008 Coordonnées GPS Lambert 93. 55 records from Royal Belgian Institute of Natural Sciences marine Chelicerata collection. 992 records from Appui technique et scientifique aux réserves naturelles (nationales et régionales) - Données ANA - CEN Ariège sur la RNR du massif de Saint-Barthélémy. 668 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 275 records from Plans de gestion du réseau de sites remarquables en Haute-Vienne - Inventaire initial du plan de gestion : Données bibliographiques. 30 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 6 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 37 records from uncultured bacterium Targeted Locus (Loci). 98 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste SENECAL Didier provenant de la base de donnée du SINP Île-de-France CETTIA. 115 records from Base BOMBINA du Parc Naturel régional Lorraine - Observations individuelles - Parc naturel régional de Lorraine. 6 records from Plan de gestion 2019 - 2023 de la Réserve Naturelle Régionale de l’Étang de Chourroumillas (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par plaques) réalisées par le CEN Nouvelle-Aquitaine. 10837 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données d'observateurs divers (observateurs transmettant un nombre de données peu élevé) saisies dans Cettia-idf. 4 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 806 records from Pollen analysis of sediment profile BLA00 from Blankensee. 7 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Olivier VILLEPOUX. 6 records from Galathea II, Danish Deep Sea Expedition 1950-52. 3 records from NCSM Non-molluscan Invertebrates Collection. 870 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 7088 records from CeDoc de Biodiversitat Vegetal: BCB-bryo. 3 records from SPF - Herbário da Universidade de São Paulo. 61 records from Diptera Eastern Fennoscandia (Luomus). 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Elsa ALFONSI. 15 records from Plan de gestion 2017 - 2021 du verger de Villebramar (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 297 records from Stadtpark Herzberg (Elster). 131 records from Unser Schulhof - eine Apotheke. 821 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle turque 1998 - 2002 Coordonnées GPS Lambert 93. 2 records from 1ère phase d'animation (2017 - 2020) des Documents d’objectifs des sites Natura 2000 FR7200665 "Coteaux calcaires de Proissans, Sainte-Nathalène et Saint-Vincent-le-Paluel", FR7200672 "Coteaux calcaires du Causse de Daglan et de la Vallée du Céou" et FR7200676 "Coteaux calcaires de Borrèze" (24) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 1 records from Additional records of Elasmopus vachoni Mateus & Mateus, 1966 (Crustacea: Amphipoda: Maeridae) from European waters (Tarifa, southern Spain). 2 records from Black grouse national surveys. 78 records from Lice (Phthiraptera) of Ireland. 1 records from B herbarium - Botanischer Garten und Botanisches Museum Berlin-Dahlem Herbarium - Herbário Virtual REFLORA. 160574 records from Bacterial diversity and community composition in grassland and forest soils of the German Biodiversity Exploratories. 8 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Arnaud BELLANGER. 23 records from Données d'observation d'écrevisses exotiques envahissantes en Nouvelle Aquitaine sur la période 2014 à 2018. 80 records from HUFU herbarium - Universidade Federal de Uberlândia - Herbário Virtual REFLORA. 11 records from HU
Keywords: GBIF; biodiversity; species occurrences